A climate services organization supporting coastal resilience: lessons from the Stone Living Lab - K. A. Dafforn; M. Borrelli; K. Bosma; J. E. K. Byrnes; L. Castro-Diaz; R. F. Chen; J. Christo; D. Cook; F. Peri; R. Shoer; M. Albert; K. Bradley; et al. (Climatic Change, 2026)
There is a growing recognition that effective climate adaptation requires organizations that can translate science into policy-relevant, place-based implementation. The Stone Living Lab (SLL) was established as a climate services organization to help bridge the gap between climate adaptation research and real-world application. In this paper, we present the Lab as a model for how universities and NGOs can partner with government agencies, Indigenous groups, and local communities to strengthen coastal resilience, highlighting the structures, guiding principles and lessons learned over the last five years. Four guiding principles shape and distinguish the Lab’s approach, extending beyond the traditional focus on science and engineering research to also include climate preparedness, education and outreach and policy engagement. These principles continue to evolve in response to experience, particularly in navigating complex partnerships and engaging with stakeholder networks, which require sustained coordination, clear communication, and intentional alignment of roles, expectations, and timelines. Other lessons highlight the importance of visible, place-based solutions, knowledge sharing and maintaining a clear mission focus while balancing short-term outcomes with long-term resilience goals. Our aim here is to provide practical insights for researchers, practitioners and managers seeking to design or strengthen similar climate services organizations.

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

A systems modelling approach to predict biological responses to extreme heat - Daniel W.A. Noble; Margaret M. Mayfield; Ary A. Hoffmann; Zhong-Hua Chen; Steven J. Lade; Xuemei Bai; Danielle A. Way; Belinda E. Medlyn; Owen K. Atkin; Adrienne B. Nicotra; James M. Cook; Brajesh K. Singh; et al. (Trends in Ecology & Evolution, 2026)

Precision Forestry: Using Machine Learning and LiDAR to Inform Thinning in Pinus taeda Plantations – A Case Study - Erik Platt; David R. Carter; Amith Reddy; Timothy J. Albaugh; Rachel L. Cook; Otávio Campoe; Rafael Rubilar; Gunjan Barua; Matthew J. Sumnall (Journal of Forestry, 2026)
We demonstrate that the inputs and conceptual foundation needed for individual-tree-level precision thinning optimization algorithms are already available. As more resource managers adopt LiDAR-based inventories, precision thinning can become a value-added outcome of collecting these data. We use LiDAR to assess individual-tree stem volumes in Pinus taeda L. plantations in the southeast US. Rather than arbitrarily selecting starting rows in row thinning operations, we use field- and LiDAR-derived stem volume data to inform row selection. Among all three study sites, row-to-row tree volume variability was present, indicating that selecting rows to be removed deliberately could improve thinning outcomes. A machine learning model based on LiDAR-derived metrics was also accurate in estimating individual stem volume in the primary study site and LiDAR was accurate in measuring pre- and post-thinning stem counts, the data that would be needed to audit thins.

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Collaborative evaluation of in silico predictions for high throughput toxicokinetics - John F. Wambaugh; Nisha S. Sipes; Gilberto Padilla Mercado; Jon A. Arnot; Linda Bertato; Trevor N. Brown; Nicola Chirico; Christopher Cook; Daniel E. Dawson; Sarah E. Davidson-Fritz; Stephen S. Ferguson; Michael-Rock Goldsmith; et al. (Toxicology in Vitro, 2026)

Associations of endocrine disrupting chemical biomarkers and their mixture with vitamin D biomarker concentrations in childhood: The HOME Study - Katherine M. Marquess; Jordan R. Kuiper; Taylor M. Etzel; Bruce P. Lanphear; Andrew N. Hoofnagle; Antonia M. Calafat; Julianne Cook Botelho; Maria Ospina; Andreas Sjodin; Lesliam Quirós-Alcalá; Kim M. Cecil; Aimin Chen; et al. (Environmental Research, 2026)

Exploring Marine Mammal Cognition as a Conservation Tool - Gordon B. Bauer; Peter F. Cook; Heidi E. Harley; Jason Bruck; Mel Cosentino; Charles J. Deutsch; Nicola Erdsack; Wendi Fellner; Tabitha Gunnars; Heather Manitzas Hill; Sonia V. Kumar; Malin K. Lilley; et al. (Marine Mammal Science, 2026)
Cognition is an animal's real‐time adaptation system for responding to change. Rapid environmental change, often anthropogenic, is expanding the range and severity of challenges confronting wild animals. Effective conservation requires a multifaceted approach that includes animals' capacities. Large‐brained, long‐lived animals such as marine mammals often have extensive capability to adaptively modify their behavior due to their cognition, which comprises the mechanisms of information acquisition, processing, and flexible action. Consequently, current behavior need not be a final predictor of future behavior for these animals. This flexibility provides an underutilized and under examined point of leverage for humans interested in improving life outcomes for wild animals. In this team‐written, interdisciplinary paper, we argue that application of cognitive approaches may facilitate many conservation efforts directed toward marine mammals. Starting with a workshop on this topic at the 24th Biennial Conference on the Biology of Marine Mammals, scientists representing a wide range of disciplinary expertise addressed eight different conservation concerns for six marine mammal species and provided potential cognitive explanations of and interventions aimed at related behavior. Our treatment highlights the value of integrated laboratory and field research, and the importance of tight lines of communication between scientists and conservation managers.

Rethinking adaptation interventions in agricultural systems for sustainability - Sechindra Vallury; Donald R Nelson; Nathan J Cook (Current Opinion in Environmental Sustainability, 2025)

The impacts of marine heatwaves on ecosystems and fisheries in Aotearoa New Zealand - Katie M. Cook; Matthew R. Dunn; Erik Behrens; Matt H. Pinkerton; Cliff S. Law; Vonda J. Cummings (New Zealand Journal of Marine and Freshwater Research, 2025)
Marine heatwaves (MHWs) are increasing in frequency and intensity globally, yet the impacts of such extreme events are not well understood. We review the effects of MHWs on the fisheries and ecosystems of Aotearoa‐New Zealand (NZ), an island nation with over 15,000 km of coastline, and 4 million km 2 of exclusive economic zone, that supports diverse marine communities and valuable commercial and recreational fisheries. Using Aotearoa‐NZ and global literature, we discuss the potential effects of MHWs on the physical environment and on species, populations and ecosystems. We review recorded national impacts with a fisheries focus, and systematically assess MHW effects on 32 commercially or culturally important Aotearoa‐NZ wild‐caught fishery or aquaculture species, classifying their vulnerabilities. We found records of MHW‐induced ecosystem shifts, with macroalgae community change, and out‐of‐range occurrences of warm‐water species. Of the 32 species examined, national MHW impacts were documented for three species (green‐lipped mussel, snapper, and Chinook salmon). We highlight the paucity of information for life‐stage specific impacts, and indirect impacts such as changes in predator‐prey interactions and biogenic habitat distributions. Assessing MHW impacts through a fisheries lens highlights the need for enhanced interdisciplinary research and monitoring, to develop sustainable management strategies under environmental change.

Precision forestry in actively managed loblolly pine plantations: Leaf area index response one growing season following a variable-rate fertilization - Chris W. Cohrs; Al Lyons; Timothy J. Albaugh; David R. Carter; Otávio C. Campoe; Rafael A. Rubilar; Matthew Sumnall; Andrew Trlica; Mark V. Corrao; Simerjeet Virk; Rex Lester; Rachel L. Cook (Forest Ecology and Management, 2025)

Characteristics of aqueous film forming foam (AFFF) sites impacted with per- and polyfluoroalkyl substances (PFAS): A 37-site study - Poonam R. Kulkarni; Nicolette E. Andrzejczyk; Arun Gavaskar; Abigail Cartwright; David T. Adamson; John Cook; Charles J. Newell (Water Research, 2025)

Predicting the yield of Pinus taeda (L.) using UAV LiDAR data in random forest and support vector machine models - Gunjan Barua; David R. Carter; Valerie A. Thomas; P. Corey Green; Phil Radtke; Thomas J. Pingel; Rachel L. Cook; Timothy J. Albaugh; Rafael Rubilar; Otavio Campoe; Matthew Sumnall (Forest Ecology and Management, 2025)

Quantifying above- and belowground biomass improved our understanding of site differences and demonstrated the importance of management decisions in sequestering carbon in Pinus taeda - Timothy J. Albaugh; Chris A. Maier; Otávio C. Campoe; Marshall A. Laviner; Timothy J. Shively; Vitor Aguiar; Kyle R. Peer; David R. Carter; Rachel L. Cook; Rafael A. Rubilar; Thomas R. Fox (Forest Ecology and Management, 2025)

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Network of networks: Time series clustering of AmeriFlux sites - David E Reed; Housen Chu; Brad G. Peter; Jiquan Chen; Michael Abraha; Brian Amiro; Ray G. Anderson; M. Altaf Arain; Paulo Arruda; Greg A. Barron-Gafford; Carl Bernacchi; Daniel P. Beverly; et al. (Agricultural and Forest Meteorology, 2025)

Ecosystem-wide PFAS characterization and environmental behavior at a heavily contaminated desert oasis in the southwestern U.S. - Jean-Luc E. Cartron; Chauncey R. Gadek; Jonathan L. Dunnum; Christopher C. Witt; Mariel L. Campbell; Samuel J. Romero; Andrew B. Johnson; Julie Kutz; Christopher Wolf; Sarah J. Choyke; Joseph A. Cook (Environmental Research, 2025)

Varying climate signals embedded in latewood blue intensity along an elevational gradient: A multi-species case study from the Great Basin, Nevada, USA - Karen E. King; Edward R. Cook; Paul J. Krusic; Daniel J. King (Dendrochronologia, 2025)

Evaluating individual tree metrics calculated from unmanned aerial vehicle laser scanning as input to a conventional growth and yield model - Matthew J. Sumnall; David R. Carter; Timothy J. Albaugh; Rachel L. Cook; Otávio C. Campoe; Rafael A. Rubilar (International Journal of Remote Sensing, 2025)

Correcting the heartwood-sapwood transition in blue intensity measurements with change point detection methods - Hung T.T. Nguyen; Rory Abernethy; Rob Wilson; Daniel L. Druckenbrod; Kathryn J. Allen; Brendan M. Buckley; Edward R. Cook; Rosanne D’Arrigo; Jonathan G. Palmer (Dendrochronologia, 2025)

Native Australian seedlings exhibit novel strategies to acclimate to repeated heatwave events - Philippa R. Alvarez; Rosalie J. Harris; Alicia M. Cook; Verónica F. Briceño; Adrienne B. Nicotra; Andrea Leigh (Oecologia, 2025)
Heatwaves are becoming more intense and frequent. Plant photosystem thermal thresholds can vary with species, but also shift in response to environmental triggers. Both upper and lower thresholds can acclimate to repeated heatwaves through ecological stress memory, where prior exposure primes them for subsequent events. The extent to which acclimation to repeated heat stress events varies among environmental origin and/or species is unknown. Different acclimation strategies might reflect biome of origin, or may be species-specific. For 12 species from two contrasting biomes—extreme desert and benign coastal temperate—we investigated responses to two simulated heatwaves, via shifts in upper and lower critical temperatures of photosystem II, and the difference between these thresholds, thermal tolerance breadth (TTB). Biome of origin had no effect on thermal tolerance. Observed differences among species following heat events suggested two possible acclimatory strategies. In some cases, species increased thermal thresholds during the first heatwave, but at the cost of reduced thermal tolerance during the second heatwave, a sprinter strategy. Other species acclimated to the first heatwave and further increased thermal tolerance to a second heatwave, indicative of ecological stress memory, a marathoner strategy. Synthesis: these among-species responses to heatwaves could suggest distinct vulnerabilities and resilience to repeat heat stress events, with some species having limited capacity to tolerate consecutive heatwaves, possibly as the cost of acclimation is too great, with other species having the advantage of increased tolerance via stress memory, helping them survive future stress, at least in the short-term.

Correction to: Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2025)

Rhenium-osmium and oxygen isotope homogeneity during the 2022 Mauna Loa eruption and implications for basaltic magma storage - Emily A. Rhoads; Anton Kutyrev; Ilya N. Bindeman; Kendra J. Lynn; Frank A. Trusdell; Drew T. Downs; Hunter R. Edwards; Geoffrey W. Cook; James M. D. Day (Bulletin of Volcanology, 2025)
Mauna Loa is one of the largest and most active volcanoes on Earth. The most recent eruption of Mauna Loa started on 27 November 2022, lasted for 13 days, and was preceded by the longest repose time of 38 years in its modern history. In this contribution, new trace- and highly siderophile-element (HSE: Os, Ir, Ru, Pt, Pd, Re) abundances, 187 Re- 187 Os, and 18 O/ 16 O data are reported for the 2022 lavas. These lavas have a limited range of MgO (6.2 ± 0.1 wt.%) and Ni (83 ± 2 µg/g), with a broader range of Re (0.3 to 1.3 ng/g) and consistent Os (0.031 to 0.080 ng/g) contents. They have 187 Os/ 188 Os ratios (0.1345 to 0.1385) which are, on average, more radiogenic than Mauna Loa picrites (0.1331 to 0.1349) and are similar in composition to more differentiated Mauna Loa tholeiite lavas (0.1340 to 0.1381). The oxygen isotope compositions of glassy samples are 5.35 ± 0.15‰ ( n = 13) and span a range in δ 18 O of + 5.0 to + 5.5‰, with an average composition 0.2 to 0.3‰ lower than MORB. The δD value is − 81 ± 11‰ ( n = 5) at very low (0.03 ± 0.015 wt.%) H 2 O concentrations. The 2022 Mauna Loa eruption is similar in terms of δ 18 O but contrasts in terms of 187 Os/ 188 Os variability, with the recent longer-lived eruptions on La Palma (Canary Islands; 85 days) in 2021 and on the Reykjanes Peninsula (Iceland) that began in 2021 and are still ongoing. Initial lavas were more fractionated for both the Canary Islands and Iceland eruptions, producing more radiogenic Os isotope compositions than later erupted products. The 2022 Mauna Loa eruption showed no such trends. The limited range in isotope compositions of the 2022 Mauna Loa lavas and their strongly fractioned HSE patterns reflect long-term storage, crystal fractionation, and assimilation of related basaltic volcanic edifice materials by the parent magma beneath the volcano prior to eruption triggering. Eruption of differentiated and homogeneous tholeiite lavas at the summit caldera and high on the volcano’s flank, with emplacement of accumulative picrites lower on the volcano, are consistent with neutral buoyancy arguments.

Canine proliferative sparganosis: a case report and review of larval cestodiasis in dogs - Varvara Semenova; Heather D.S. Walden; Kelsey Bollenback; James R. Cook; Robert J. Ossiboff (Journal of Comparative Pathology, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Remotely Sensed Fire Heterogeneity and Biomass Recovery Predicts Empirical Biodiversity Responses - Rebecca K. Gibson; Don A. Driscoll; Kristina J. Macdonald; Grant J. Williamson; Rachael H. Nolan; Tim S. Doherty; Dale G. Nimmo; Euan G. Ritchie; Mark Tozer; Liz Tasker; Aaron Greenville; Adam Roff; et al. (Global Ecology and Biogeography, 2025)
Aim To compare field‐based evidence of plant and animal responses to fire with remotely sensed signals of fire heterogeneity and post‐fire biomass recovery. Location South‐eastern Australia; New South Wales. Time Period 2019–2022. Major Taxa Studied A total of 982 species of plants and animals, in eight taxonomic groups: amphibians, birds, fish, insects, mammals, molluscs, plants and reptiles. Methods We collated 545,223 plant and animal response records from 47 field surveys of 4613 sites that focussed on areas burnt in 2019–2020. For each site, we calculated remotely sensed signals of fire heterogeneity and post‐fire biomass recovery, including the delayed recovery index. Meta‐regression analyses were conducted separately for species that declined after fire (negative effect sizes) and species that increased after fire (positive effect sizes) for each buffer size (250 m, 500 m, 1 km, 1.5 km, 2 km and 2.5 km radius). Results We found that species exposed to homogenous high‐severity fire (i.e., low fire heterogeneity) were more likely to exhibit decreased abundance/occurrence or inhibited recovery. Areas with delayed recovery of biomass also had significant negative on‐ground responses, with lower abundance or occurrence in areas where biomass recovery was slower. Main Conclusions The fire heterogeneity index and the delayed recovery index are suitable for inclusion in monitoring and reporting systems for tracking relative measures over time, particularly when field survey data is not available at the landscape scales required to support reporting and management decisions. Locations with remotely sensed signals of delayed recovery should be prioritised for protection against further disturbances that may interfere with the recovery process. Research attention must next focus on how cumulative fire heterogeneity patterns of successive fires affect the post‐fire recovery dynamics to further inform the application of remote sensing indicators as management tools for biodiversity conservation.

Reversal of practical resistance in fall armyworm to Cry1F maize: a case report on the resistance to susceptibility in Bt crops from the southeastern USA - Tiago Silva; Gregory A. Sword; Andie Miller; Jawwad A. Qureshi; Graham P. Head; Dawson D. Kerns; Juan Luis Jurat-Fuentes; James Villegas; Tyler B. Towles; Xinzhi Ni; Francis P. F. Reay-Jones; Daniel Carrillo; et al. (Journal of Pest Science, 2025)

Crown complementarity rather than crown selection contributes to stem complementarity in genetic mixtures of Pinus taeda L - David R. Carter; Timothy J. Albaugh; Matthew Sumnall; Jake J. Grossman; Otávio C. Campoe; Rachel L. Cook; Rafael A. Rubilar; Chris A. Maier; T. Adam Coates; Julia DeFeo; Grady J. Boyle; Megan Van Spanje (Acta Oecologica, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

SNAPSHOT USA 2019–2023: The First Five Years of Data From a Coordinated Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Benjamin R. Goldstein; Christopher Pate; Paula Castiblanco; Maggie E. Abell; Jessie Adley; Briana Agenbroad; Adam A. Ahlers; Peter D. Alexander; et al. (Global Ecology and Biogeography, 2025)
Motivation SNAPSHOT USA is an annual, multicontributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2019–2023 contains 987,979 records of camera trap image sequence data and 9694 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in all 50 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1st August and 29th December each year from 2019 to 2023. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2019–2023 comprises two .csv files. The original data can be found within the SNAPSHOT USA Initiative in the Wildlife Insights platform.

Comparing efficiencies of population control methods for responding to introductions of transboundary animal diseases in wild pigs - Nathan P. Snow; Benjamin Smith; Michael J. Lavelle; Michael P. Glow; Kayleigh Chalkowski; Bruce R. Leland; Sarah Sherburne; Justin W. Fischer; Keely J. Kohen; Seth M. Cook; Hatton Smith; Kurt C. VerCauteren; et al. (Preventive Veterinary Medicine, 2024)

Growth trends of loblolly pine age five or less in relation to soil type and management intensity - Christen Beasley; David R. Carter; Timothy J. Albaugh; David Enemo; Daniel S. Hong; Rachel Cook; Otávio Campoe; Rafael Rubilar (Forest Ecology and Management, 2024)

Nature vs. nurture: Drivers of site productivity in loblolly pine (Pinus taeda L.) forests in the southeastern US - Vicent A. Ribas-Costa; Aitor Gastón; Sean A. Bloszies; Jesse D. Henderson; Andrew Trlica; David R. Carter; Rafael Rubilar; Timothy J. Albaugh; Rachel L. Cook (Forest Ecology and Management, 2024)

Threat assessment for Pacific sand lance (Ammodytes personatus) in the Salish Sea - Jacqueline R. Huard; Victoria Hemming; Matthew R. Baker; Jennifer Blancard; Ian Bruce; Sarah Cook; Gail K. Davoren; Phillip Dionne; Virginia East; J. Mark Hipfner; Nicola R. Houtman; Brian A. Koval; et al. (Frontiers in Marine Science, 2024)
Like many forage fish species, Pacific sand lance ( Ammodytes personatus ) play a key role in nearshore marine ecosystems as an important prey source for a diverse array of predators in the northeastern Pacific. However, the primary threats to Pacific sand lance and their habitat are poorly defined due to a lack of systematic data. Crucial information needed to assess their population status is also lacking including basic knowledge of their local and regional abundance and distribution. Sand lance are currently listed as ‘not evaluated’ under the IUCN red list and they have not been assessed by US and Canadian agencies. This hampers management and policy efforts focused on their conservation. To address this knowledge gap, we conducted a three-part, structured expert elicitation to assess the vulnerability of Salish Sea sand lance populations. Experts were asked to list and rank key threats to Salish Sea sand lance and/or their habitat, to further quantify the vulnerability of sand lance to identified threats using a vulnerability matrix, and to predict the population trajectory in 25 years from today. Impacts associated with climate change (e.g. sea level rise, sea temperature rise, ocean acidification, and extreme weather) consistently ranked high as threats of concern in the ranking exercise and quantified vulnerability scores. Nearly every expert predicted the population will have declined from current levels in 25 years. These results suggest sand lance face numerous threats and may be in decline under current conditions. This research provides vital information about which threats pose the greatest risk to the long-term health of sand lance populations and their habitat. Managers can use this information to prioritize which threats to address. Future research to reliably quantify population size, better understand the roles of natural and anthropogenic impacts, and to identify the most cost-effective actions to mitigate multiple threats, is recommended.

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

A new certified reference material IAEA-465 for radionuclides in Baltic Sea sediment - M.K. Pham; M.-O. Aust; J. Bartocci; O. Blinova; F.P. Carvalho; E. Chamizo; M. Cook; D. Degering; M. Fujak; C. Gascó; R. Gurriaran; V. Jobbágy; et al. (Journal of Environmental Radioactivity, 2024)

Evaluating the transferability of airborne laser scanning derived stem size prediction models for Pinus taeda L. stem size estimation to two different locations and acquisition specifications - Matthew J. Sumnall; David R. Carter; Timothy J. Albaugh; Erik Platt; Trevor Host; Rachel L. Cook; Otávio C. Campoe; Rafael A. Rubilar (International Journal of Remote Sensing, 2024)

Correction to: Drought and deluge: the recurrence of hydroclimate extremes during the past 600 years in eastern Australia’s Natural Resource Management (NRM) clusters - Jonathan G. Palmer; Danielle Verdon‑Kidd; Kathryn J. Allen; Philippa Higgins; Benjamin I. Cook; Edward R. Cook; Christian S. M. Turney; Patrick J. Baker (Natural Hazards, 2024)

Extraordinary levels of per- and polyfluoroalkyl substances (PFAS) in vertebrate animals at a New Mexico desert oasis: Multiple pathways for wildlife and human exposure - Christopher C. Witt; Chauncey R. Gadek; Jean-Luc E. Cartron; Michael J. Andersen; Mariel L. Campbell; Marialejandra Castro-Farías; Ethan F. Gyllenhaal; Andrew B. Johnson; Jason L. Malaney; Kyana N. Montoya; Andrew Patterson; Nicholas T. Vinciguerra; et al. (Environmental Research, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Mid-to Late Holocene East Antarctic ice-core tephrochronology: Implications for reconstructing volcanic eruptions and assessing their climatic impacts over the last 5,500 years - Peter M. Abbott; Joseph R. McConnell; Nathan J. Chellman; Sepp Kipfstuhl; Maria Hörhold; Johannes Freitag; Eliza Cook; William Hutchison; Michael Sigl (Quaternary Science Reviews, 2024)

Moderate D/H ratios in methane ice on Eris and Makemake as evidence of hydrothermal or metamorphic processes in their interiors: Geochemical analysis - Christopher R. Glein; William M. Grundy; Jonathan I. Lunine; Ian Wong; Silvia Protopapa; Noemi Pinilla-Alonso; John A. Stansberry; Bryan J. Holler; Jason C. Cook; Ana Carolina Souza-Feliciano (Icarus, 2024)

Measurement of D/H and 13C/12C ratios in methane ice on Eris and Makemake: Evidence for internal activity - W.M. Grundy; I. Wong; C.R. Glein; S. Protopapa; B.J. Holler; J.C. Cook; J.A. Stansberry; J.I. Lunine; A.H. Parker; H.B. Hammel; S.N. Milam; R. Brunetto; et al. (Icarus, 2024)

Forest soil classification for intensive pine plantation management: “Site Productivity Optimization for Trees” system - Rachel Cook; Thomas R. Fox; Howard Lee Allen; Chris W. Cohrs; Vicent Ribas-Costa; Andrew Trlica; Matthew Ricker; David R. Carter; Rafael Rubilar; Otávio Campoe; Timothy J. Albaugh; Pete Kleto; et al. (Forest Ecology and Management, 2024)

Drought and deluge: the recurrence of hydroclimate extremes during the past 600 years in eastern Australia’s Natural Resource Management (NRM) clusters - Jonathan G. Palmer; Danielle Verdon-Kidd; Kathryn J. Allen; Philippa Higgins; Benjamin I. Cook; Edward R. Cook; Christian S. M. Turney; Patrick J. Baker (Natural Hazards, 2024)
Recent extremes of flood and drought across Australia have raised questions about the recurrence of such rare events and highlighted the importance of understanding multi-decadal climate variability. However, instrumental records over the past century are too short to adequately characterise climate variability on multi-decadal and longer timescales or robustly determine extreme event frequencies and their duration. Palaeoclimate reconstructions can provide much-needed information to help address this problem. Here, we use the 600-year hydroclimate record captured in the eastern Australian and New Zealand Drought Atlas (ANZDA) to analyse drought and pluvial frequency trends for East Australian Natural Resource Management (NRM) clusters. This partitioning of the drought atlas grid points into recognised biophysical areas (i.e. NRM clusters) revealed their differences and similarities in drought intensity and pluvial events over time. We find sustained multi-decadal periods of a wet–dry geographic 'seesaw' between eastern to central and southern NRMs (e.g. 1550–1600 CE and 1700–1750 CE). In contrast, other periods reveal spatially consistent wetting (e.g. 1500–1550 CE) or drying (e.g. 1750–1800 CE). Emerging hot spot analysis further shows that some areas that appear naturally buffered from severe drought during the instrumental period have a greater exposure risk when the longer 600-year record is considered. These findings are particularly relevant to management plans when dealing with the impacts of climate extremes developed at regional scales. Our results demonstrate that integrating and extending instrumental records with palaeoclimate datasets will become increasingly important for developing robust and locally specific extreme event frequency information for managing water resources.

Visualization of radiographic mineral opacities in guinea pigs in the location of the bulbourethral glands may be underdiagnosed - Amanda D. Wong; Krista A. Keller; Anthony J. Cerreta; Kirstin Cook; Joanna K. Webb; Kenneth R. Welle; Martha A. Delaney; Audrey Billhymer (Journal of Exotic Pet Medicine, 2024)

Horizon scanning of potential threats to high‐Arctic biodiversity, human health and the economy from marine invasive alien species: A Svalbard case study - Elizabeth J. Cottier‐Cook; Jude Bentley‐Abbot; Finlo R. Cottier; Dan Minchin; Sergej Olenin; Paul E. Renaud (Global Change Biology, 2024)
The high Arctic is considered a pristine environment compared with many other regions in the northern hemisphere. It is becoming increasingly vulnerable to invasion by invasive alien species (IAS), however, as climate change leads to rapid loss of sea ice, changes in ocean temperature and salinity, and enhanced human activities. These changes are likely to increase the incidence of arrival and the potential for establishment of IAS in the region. To predict the impact of IAS, a group of experts in taxonomy, invasion biology and Arctic ecology carried out a horizon scanning exercise using the Svalbard archipelago as a case study, to identify the species that present the highest risk to biodiversity, human health and the economy within the next 10 years. A total of 114 species, currently absent from Svalbard, recorded once and/or identified only from environmental DNA samples, were initially identified as relevant for review. Seven species were found to present a high invasion risk and to potentially cause a significant negative impact on biodiversity and five species had the potential to have an economic impact on Svalbard. Decapod crabs, ascidians and barnacles dominated the list of highest risk marine IAS. Potential pathways of invasion were also researched, the most common were found associated with vessel traffic. We recommend (i) use of this approach as a key tool within the application of biosecurity measures in the wider high Arctic, (ii) the addition of this tool to early warning systems for strengthening existing surveillance measures; and (iii) that this approach is used to identify high‐risk terrestrial and freshwater IAS to understand the overall threat facing the high Arctic. Without the application of biosecurity measures, including horizon scanning, there is a greater risk that marine IAS invasions will increase, leading to unforeseen changes in the environment and economy of the high Arctic.

Neurodevelopmental outcomes in children and adults with Fetal Valproate Spectrum Disorder: A contribution from the ConcePTION project - M. Bluett-Duncan; D. Astill; R. Charbak; J. Clayton-Smith; S. Cole; P.A. Cook; J. Cozens; K. Keely; J. Morris; R. Mukherjee; E. Murphy; P. Turnpenny; et al. (Neurotoxicology and Teratology, 2023)

Drought conditioning of rhizosphere microbiome influences maize water use traits - Kelsey R. Carter; Abigael C. Nachtsheim; L. Turin Dickman; Eric R. Moore; Sangeeta Negi; John P. Heneghan; Anthony J. Sabella; Christina R. Steadman; Michaeline B. N. Albright; Christine M. Anderson-Cook; Louise H. Comas; Rose J. Harris; et al. (Plant and Soil, 2023)
Background and Aims Beneficial plant–microbe interactions can improve plant performance under drought; however, we know less about how drought-induced shifts in microbial communities affect plant traits. Methods We cultivated Zea mays in fritted clay with soil microbiomes originating from contrasting environments (agriculture or forest) under two irrigation treatments (well-watered or water limited). Using this design, we investigated whether water conditioning was carried forward through the microbiome to affect a subsequent plant cohort that was subjected to either a well-watered or water limited treatment. Results Regardless of the microbiome-origin, plants inoculated with a microbiome from a water limited legacy had traits that allowed them to avoid stress but conserve water. They produced longer roots to explore soil, generated greater soil dissolved organic carbon, potentially stimulating the microbiome, and slower soil water content loss during drought. A well-watered legacy resulted in plants that delayed permanent stomatal closure and higher photosynthetic nitrogen use efficiency. In plants with a forest-originated microbiome, a well-watered legacy and water treatment also resulted in higher rates of photosynthesis and stomatal conductance. Conclusion These results demonstrate that soil microbiomes can be developed to influence plant drought performance, impacting crop resilience, using short-term microbial conditioning.

Development and Validation of an Abbreviated Child and Adult Food Security Scale for Use in Clinical and Research Settings in the United States - Ana Poblacion; Stephanie Ettinger de Cuba; Deborah A. Frank; Georgiana Esteves; Lindsey J. Rateau; Timothy C. Heeren; Sharon Coleman; Maureen M. Black; Diana B. Cutts; Félice Lê-Scherban; Eduardo R. Ochoa; Megan Sandel; et al. (Journal of the Academy of Nutrition and Dietetics, 2023)

Using in-situ strain measurements to evaluate the accuracy of stress estimation procedures from fracture injection/shut-in tests - Yves Guglielmi; Mark McClure; Jeffrey Burghardt; Joseph P. Morris; Thomas Doe; Pengcheng Fu; Hunter Knox; Vince Vermeul; Tim Kneafsey; J. Ajo-Franklin; T. Baumgartner; K. Beckers; et al. (International Journal of Rock Mechanics and Mining Sciences, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Assay measurement of gaseous UF6 using femtosecond laser-induced breakdown spectroscopy in the 424.4 nm spectral region - Benjamin S. Jordan; Jason D. Readle; Jeffrey R. Cooper; Matthew Cook; Jason P. Hayward; J. Daniel Hartman; Dean Forrest; Howard L. Hall (Annals of Nuclear Energy, 2023)

The Diversity of Eucheumatoid Seaweed Cultivars in the Philippines - Richard V. Dumilag; Bea A. Crisostomo; Zae-Zae A. Aguinaldo; Lourie Ann R. Hinaloc; Lawrence M. Liao; Hilly Ann Roa-Quiaoit; Floredel Dangan-Galon; Giuseppe C. Zuccarello; Marie-Laure Guillemin; Juliet Brodie; Elizabeth J. Cottier-Cook; Michael Y. Roleda (Reviews in Fisheries Science & Aquaculture, 2023)

Estimation of individual stem volume and diameter from segmented UAV laser scanning datasets in Pinus taeda L. plantations - Matthew J. Sumnall; Timothy J. Albaugh; David R. Carter; Rachel L. Cook; W. Cully Hession; Otávio C. Campoe; Rafael A. Rubilar; Randolph H. Wynne; Valerie A. Thomas (International Journal of Remote Sensing, 2023)

Grazing, egg production and carbon budgets for Calanus finmarchicus across the Fram Strait - Holly E. Jenkins; Florence Atherden; Kathryn B. Cook; Thomas R. Anderson; Barry Thornton; Elaine Mitchell; Elodie Jacob; Daniel J. Mayor (Frontiers in Marine Science, 2022)
Calanoid copepods comprise around 90% of Arctic zooplankton biomass and are fundamental to the ecological and biogeochemical functioning of high-latitude pelagic ecosystems. They accumulate lipid reserves during the productive months and represent an energy-rich food source for higher trophic levels. Rapidly changing climate in the Arctic may alter the quantity and composition of the food environment for one of the key copepod species, Calanus finmarchicus , with as yet unquantified effects on its production. Here we present rates of feeding and egg production in female C. finmarchicus exposed to the range of feeding conditions encountered across the Fram Strait in May/June 2018. Carbon (C) budgets were constructed and used to examine the relationship between feeding and growth (= egg production) in these animals. C-specific ingestion rates (mean ± standard deviation) were highly variable, ranging from 0.015 ± 0.004 to 0.645 ± 0.017 day -1 (mean = 0.295 ± 0.223 day -1 ), and were positively correlated with food availability. C-specific egg production rates ranged from 0.00 to 0.049 day -1 (mean = 0.012 ± 0.011) and were not correlated with either food availability or ingestion rate. Calculated gross growth efficiencies (GGE: growth/ingestion) were low, 0.12 ± 0.13 (range = 0.01 to 0.39). The assembled C budgets indicate that the average fraction of ingested food that was surplus to the requirements for egg production, respiration and losses to faecal pellets was 0.17 ± 0.42. We suggest that this excess occurred, at least in part, because many of the incubated females were still undergoing the energetically (C-) expensive process of gonad maturation at the time of sampling, an assertion that is supported by the relatively high C:N (nitrogen) ratios of the incubated females, the typically low egg production rates, and gonad maturation status. Ontogenetic development may thus explain the large variability seen in the relationship between egg production and ingestion. The apparently excessive ingestion rates may additionally indicate that recently moulted females must acquire additional N via ingestion to complete the maturation process and begin spawning. Our results highlight the need for improved fundamental understanding of the physiology of high-latitude copepods and its response to environmental change.

Influence of coating type, colour, and deployment timing on biofouling by native and non-native species in a marine renewable energy context - Christopher R. Nall; Marie-Lise Schläppy; Elizabeth J. Cottier-Cook; Andrew J. Guerin (Biofouling, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Carbon and Lipid Contents of the Copepod Calanus finmarchicus Entering Diapause in the Fram Strait and Their Contribution to the Boreal and Arctic Lipid Pump - Geraint A. Tarling; Anna Belcher; Mayleen Blackwell; Claudia Castellani; Kathryn Barbara Cook; Finlo R. Cottier; Victoria Dewar-Fowler; Jennifer J. Freer; Laura Gerrish; Magnus L. Johnson; Kim S. Last; Penelope Kate Lindeque; et al. (Frontiers in Marine Science, 2022)
The boreal copepod Calanus finmarchicus sequesters substantial amounts of carbon (C) in the deep layers of the North Atlantic Ocean through their contribution to the “lipid pump.” This pump is driven by these zooplankton descending from the surface layers to spend prolonged periods at depth during which time they metabolise substantial lipid reserves and a fraction suffer mortality. C. finmarchicus is principally a boreal species but is expatriated by currents flowing northwards into Arctic regions such as the Fram Strait, where it is now able to complete its life cycle. We considered how this expansion to its distributional range adds to the estimated magnitude of the lipid pump. Field sampling in the Fram Strait found C. finmarchicus abundance to be spatially variable with high values, equivalent to those reported for core distributional areas further south, found mainly in the eastern region. Lipid reserve levels were sufficient for many individuals to survive the overwintering period and reproduce the following spring. In accordance with abundance patterns, lipid pump magnitude was greater in the Eastern Fram Strait (2.04 g C m −2 year −1 ) compared to the Western Fram Strait (0.33 g C m −2 year −1 ). At least for the eastern region, these rates are similar to those reported for this species elsewhere (average of 4.35 g C m −2 year −1 ). When extrapolated to the wider spatial area of the Fram Strait, the lipid pump generated by this species in this ocean sector amounts to 0.3 Mt C year −1 . Although constituting a modest proportion of the total C. finmarchicus lipid pump of 19.3 Mt C year −1 , it indicates that the continued northwards expansion of this species will act to increase the size of its lipid pump, which may counteract that lost through the northwards retreat of its Arctic congeners, Calanus glacialis and Calanus hyperboreus .

Biomass Turnover Rates in Metabolically Active and Inactive Marine Calanoid Copepods - Daniel J. Mayor; Kathryn B. Cook; Barry Thornton; Florence Atherden; Geraint A. Tarling; Thomas R. Anderson (Frontiers in Marine Science, 2022)
Lipid-storing copepods are fundamental to the functioning of marine ecosystems, transferring energy from primary producers to higher trophic levels and sequestering atmospheric carbon (C) in the deep ocean. Quantifying trophic transfer and biogeochemical cycling by copepods requires improved understanding of copepod metabolic rates in both surface waters and during lipid-fueled metabolism over winter. Here we present new biomass turnover rates of C and nitrogen (N) in Calanoides acutus , Calanoides natalis , Calanus glacialis and Calanus hyperboreus alongside published data for Calanus finmarchicus and Calanus pacificus . Turnover rates in metabolically active animals, normalised to 10°C, ranged between 0.007 – 0.105 d -1 and 0.004 – 0.065 d -1 for C and N, respectively. Turnover rates of C were typically faster than those for N, supporting the understanding that non-protein C, e.g. lipid, is catabolised faster than protein. Re-analysis of published data indicates that inactive, overwintering C. finmarchicus turn over wax ester lipids at a rate of 0.0016 d -1 . These and other basal rate data will facilitate the mechanistic representation of copepod physiology in global biogeochemical models, thereby reducing uncertainties in our predictions of future ocean ecosystem functioning and C sequestration.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

The Open-Ocean Gulf of Mexico After Deepwater Horizon: Synthesis of a Decade of Research - Tracey T. Sutton; Rosanna J. Milligan; Kendra Daly; Kevin M. Boswell; April B. Cook; Maëlle Cornic; Tamara Frank; Kaitlin Frasier; Daniel Hahn; Frank Hernandez; John Hildebrand; Chuanmin Hu; et al. (Frontiers in Marine Science, 2022)
The scale of the Deepwater Horizon disaster was and is unprecedented: geographic extent, pollutant amount, countermeasure scope, and of most relevance to this Research Topic issue, range of ecotypes affected. These ecotypes include coastal/nearshore, continental shelf, deep benthic, and open-ocean domains, the last of which is the subject of this synthesis. The open-ocean ecotype comprises ~90% of the volume of the Gulf of Mexico. The exact percentage of this ecotype contaminated with toxins is unknown due to its three-dimensional nature and dynamics, but estimates suggest that the footprint encompassed most of its eastern half. Further, interactions between the water column and the deep benthos may be persistent, making this synthesis one of time (a decade) rather than event conclusion. Here we examine key elements of the open-ocean ecosystem, with emphasis on vulnerability and resilience. Of paramount importance relative to the Gulf nearshore and shelf ecotypes, pre-disaster baseline data were lacking for most of the fauna. In such cases, inferences were drawn from post-disaster assessments. Both phytoplankton and mesozooplankton vulnerabilities were quite high, but resilience appeared equally so. The phytoplankton situation was a bit more complex in that toxin-imposed reductions may have been offset by nutrient injection via high freshwater discharge in 2010. Intermediate trophic levels exhibited population-level depressions, ostensibly due to high vulnerability and low resilience. Apex predator impacts were variable. Certain large epipelagic fishes may have avoided the highest concentrations of hydrocarbons/dispersant, and thus larval abundances returned to pre-disaster levels of variability and abundance within a few years after a steep initial decline. Oceanic cetaceans, particularly shallow-diving stenellid dolphins, did not appear to avoid oiled waters and exhibited strong declines in the northern Gulf. Given that population declines of many open-ocean taxa appear to be ongoing a decade later, we conclude that this largest of Gulf ecosystem components, like its deep-benthic counterpart, is as fragile as it is voluminous. This is particularly concerning given the rapid, and likely irreversible, shift to deeper waters by the US and Mexican oil industries in concert with the higher likelihood of accidents with increasing platform depth.

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Rapid radiation of Southern Ocean shags in response to receding sea ice - Nicolas J. Rawlence; Alexander T. Salis; Hamish G. Spencer; Jonathan M. Waters; Lachie Scarsbrook; Kieren J. Mitchell; Richard A. Phillips; Luciano Calderón; Timothée R. Cook; Charles‐André Bost; Ludovic Dutoit; Tania M. King; et al. (Journal of Biogeography, 2022)
Aim Understanding how natural populations respond to climatic shifts is a fundamental goal of biological research in a fast‐changing world. The Southern Ocean represents a fascinating system for assessing large‐scale climate‐driven biological change, as it contains extremely isolated island groups within a predominantly westerly, circumpolar wind and current system. Blue‐eyed shags represent a paradoxical seabird radiation—a circumpolar distribution implies strong dispersal capacity yet their species‐rich nature suggests local adaptation and isolation. Here we attempt to resolve this paradox in light of the history of repeated cycles of climate change in the Southern Ocean. Location Southern Ocean. Taxa 16 species and subspecies of blue‐eyed shags (Phalacrocoracidae; Leucocarbo spp.). Methods We use mitochondrial and nuclear sequence data from individuals across the geographical range of the genus to conduct the first comprehensive, time‐calibrated phylogenetic analyses and ancestral‐range biogeographical reconstructions of the blue‐eyed shags. Results The origins of many island‐endemic lineages are remarkably recent, consistent with a recent high‐latitude circumpolar radiation in the Pliocene or Early Pleistocene. This recent sub‐Antarctic expansion contrasts with significantly deeper lineages detected in South America and, to a lesser extent, New Zealand. These regions, particularly South America, acted as glacial refugia and sources for multiple waves of post‐glacial dispersal. Main conclusions The blue‐eyed shag paradox is resolved, with at least two waves of dispersal, linked to interglacial cycles, explaining the current distribution and diversity. Descendants of a Pliocene or Early Pleistocene wave of dispersal out of South America survive in the New Zealand region. In contrast, taxa distributed on sub‐Antarctic islands originated much later, possibly since the Last Glacial Maximum. Blue‐eyed shags therefore represent a powerful model system—comprising several natural replicates—for studying the early stages of founder‐event speciation and adaptation in a Southern‐Ocean bird group.

The Alberta moving beyond breast cancer (AMBER) cohort study: baseline description of the full cohort - Christine M. Friedenreich; Jeff K. Vallance; Margaret L. McNeely; S. Nicole Culos-Reed; Charles E. Matthews; Gordon J. Bell; John R. Mackey; Karen A. Kopciuk; Leanne Dickau; Qinggang Wang; Diane Cook; Stephanie Wharton; et al. (Cancer Causes & Control, 2022)
Purpose The Alberta Moving Beyond B r east Cancer (AMBER) Study is an ongoing prospective cohort study investigating how direct measures of physical activity (PA), sedentary behavior (SB), and health-related fitness (HRF) are associated with survival after breast cancer. Methods Women in Alberta with newly diagnosed stage I (≥ T1c) to IIIc breast cancer were recruited between 2012 and 2019. Baseline assessments were completed within 90 days of surgery. Measurements included accelerometers to measure PA and SB; a graded treadmill test with gas exchange analysis to measure cardiorespiratory fitness (VO 2peak ); upper and lower body muscular strength and endurance; dual-X-ray absorptiometry to measure body composition; and questionnaires to measure self-reported PA and SB. Results At baseline, the 1528 participants’ mean age was 56 ± 11 years, 59% were post-menopausal, 62% had overweight/obesity, and 55% were diagnosed with stage II or III disease. Based on device measurements, study participants spent 8.9 ± 1.7 h/day sedentary, 4.4 ± 1.2 h/day in light-intensity activity, 0.9 ± 0.5 h/day in moderate-intensity activity, and 0.2 ± 0.2 h/day in vigorous-intensity activity. For those participants who reached VO 2peak , the average aerobic fitness level was 26.6 ± 6 ml/kg/min. Average body fat was 43 ± 7.1%. Conclusion We have established a unique cohort of breast cancer survivors with a wealth of data on PA, SB, and HRF obtained through both direct and self-reported measurements. Study participants are being followed for at least ten years to assess all outcomes after breast cancer. These data will inform clinical and public health guidelines on PA, SB, and HRF for improving breast cancer outcomes.

Can a key boreal Calanus copepod species now complete its life-cycle in the Arctic? Evidence and implications for Arctic food-webs - Geraint A. Tarling; Jennifer J. Freer; Neil S. Banas; Anna Belcher; Mayleen Blackwell; Claudia Castellani; Kathryn B. Cook; Finlo R. Cottier; Malin Daase; Magnus L. Johnson; Kim S. Last; Penelope K. Lindeque; et al. (Ambio, 2022)
The changing Arctic environment is affecting zooplankton that support its abundant wildlife. We examined how these changes are influencing a key zooplankton species, Calanus finmarchicus , principally found in the North Atlantic but expatriated to the Arctic. Close to the ice-edge in the Fram Strait, we identified areas that, since the 1980s, are increasingly favourable to C. finmarchicus . Field-sampling revealed part of the population there to be capable of amassing enough reserves to overwinter. Early developmental stages were also present in early summer, suggesting successful local recruitment. This extension to suitable C. finmarchicus habitat is most likely facilitated by the long-term retreat of the ice-edge, allowing phytoplankton to bloom earlier and for longer and through higher temperatures increasing copepod developmental rates. The increased capacity for this species to complete its life-cycle and prosper in the Fram Strait can change community structure, with large consequences to regional food-webs.

Effect of varied unmanned aerial vehicle laser scanning pulse density on accurately quantifying forest structure - Matthew J. Sumnall; Timothy J. Albaugh; David R. Carter; Rachel L. Cook; W. Cully Hession; Otávio C. Campoe; Rafael A. Rubilar; Randolph H. Wynne; Valerie A. Thomas (International Journal of Remote Sensing, 2022)

Eucalyptus grandis Response to Calcium Fertilization in Colombia - Zach S Grover; Rachel L Cook; Marcela Zapata; J Byron Urrego; Timothy J Albaugh; Ariel Zelaya; Tomasz Ozyhar; Rafael Rubilar; David R Carter; Otávio C Campoe (Forest Science, 2021)
Calcium (Ca) is a critical plant nutrient typically applied at the time of planting in intensive Eucalyptus plantations in South America. At two sites in Colombia, we examined (1) calcium source by comparing growth after application of 100 kg ha−1 elemental Ca as lime or as pelletized highly reactive calcium fertilizer (HRCF) compared to a no application control, and (2) Ca rate by applying 0, 100, 200, and 400 kg ha−1 elemental Ca as HRCF with the addition of nitrogen, phosphorus, potassium, sulfur, and boron (NPKSB). We assessed height, diameter, and volume after 12 and 24 months. There were no growth differences from Ca source at the 100 kg ha−1 rate. We found increased volume after 24 months at the “Popayan” site with 200 and 400 kg ha−1 Ca HRCF+NPKSB treatments (112 and 113 m3 ha−1, respectively) compared to control (92 m3 ha−1), a 22% increase. In contrast, volume did not differ after 24 months at the “Darien” site, ranging from 114 m3 ha−1 in the 0 kg ha−1 Ca HRCF+NPKSB treatment to 98 m3 ha−1 in the control. Differences in response are likely due to soil characteristics, such as organic matter, emphasizing the importance of identifying site-specific nutrient deficiencies.

Financial Returns for Biomass on Short-Rotation Loblolly Pine Plantations in the Southeastern United States - Andrew Trlica; Rachel L Cook; Timothy J Albaugh; Rajan Parajuli; David R Carter; Rafael A Rubilar (Forest Science, 2021)
Rising demand for renewable energy has created a potential market for biomass from short-rotation pine plantations in the southeastern United States. Site preparation, competition control, fertilization, and enhanced seedling genotypes offer the landowner several variables for managing productivity, but their combined effects on financial returns are unclear. This study estimated returns from a hypothetical 10-year biomass harvest in loblolly pine plantation using field studies in the Coastal Plain of North Carolina and the Virginia Piedmont testing combinations of tree genotype, planting density, and silviculture. Although enhanced varietal genotypes could yield more biomass, open-pollinated seedlings at 1,236–1,853 trees ha−1 under operational silviculture had the greatest returns at both sites, with mean whole-tree internal rates of return of 8.3%–9.9% assuming stumpage equal to current pulpwood prices. At a 5% discount rate, break-even whole-tree stumpage at the two sites in the optimal treatments was $8.72–$9.92 Mg−1, and break-even yield was 175–177 Mg ha−1 (roughly 18 Mg ha−1 yr−1 productivity), although stumpage and yield floors were higher if only stem biomass was treated as salable. Dedicated short-rotation loblolly biomass plantations in the region are more likely to be financially attractive when site establishment and maintenance costs are minimized.

Geographic variation of mercury in breeding tidal marsh sparrows of the northeastern United States - Christopher J. Sayers; Mackenzie R. Roeder; Lindsay M. Forrette; Daniel Roche; Gaetan L. B. Dupont; Sam E. Apgar; Alison R. Kocek; Alexandra M. Cook; W. Gregory Shriver; Chris S. Elphick; Brian Olsen; David N. Bonter (Ecotoxicology, 2021)

The Toxicology Investigators Consortium 2020 Annual Report - Meghan B. Spyres; Kim Aldy; Lynn A Farrugia; A. Min Kang; Jennifer S. Love; Sharan L. Campleman; Shao Li; Alexandra Amaducci; Evan Schwarz; Paul M. Wax; Jeffery Brent; J. Acciani; et al. (Journal of Medical Toxicology, 2021)

Seaweed aquaculture: a preliminary assessment of biosecurity measures for controlling the ice-ice syndrome and pest outbreaks of a Kappaphycus farm - Cicilia S. B. Kambey; Iona Campbell; Elizabeth J. Cottier-Cook; Adibi R. M. Nor; Azhar Kassim; Ahemad Sade; Phaik E. Lim (Journal of Applied Phycology, 2021)
The application of biosecurity in seaweed aquaculture plays an important role in reducing the impact of disease and pest outbreaks. The continuous occurrence of seaweed pests including the macroalgal epiphytes, epi-endophytic filamentous algae and biofilms on Kappaphycus farms may also potentially induce further incidences of the ice-ice syndrome. In this study, on-farm biosecurity management measures were tested on the commercially grown seaweeds Kappaphycus malesianus and Kappaphycus alvarezii during peak ice-ice season at Gallam-Gallam Village, Sabah, Malaysia. The investigation was focused on preventative control measures including the early detection of the ice-ice syndrome and pests through propagule health checks, regular cleaning of the crop thallus and associated long-line ropes and monitoring of the environment. Farm procedures and practices were also assessed in terms of their biosecurity ‘risk’ using the hazard analysis and critical control point (HCCAP) approach. Observations were replicated in two different farm management systems; one system adopted routine biosecurity measures and the other had no biosecurity measures. The results showed that the ice-ice syndrome and pest outbreak was significantly decreased by 60–75% for K. malesianus and 29–71% for K. alvarezii at the farm which adopted the routine biosecurity measures compared with the no biosecurity treatment. The biosecurity measures also significantly improved growth rate and seaweed quality. The infection levels of the epi-endophyte Melanothamnus sp. contributed to the ice-ice syndrome in K. malesianus , whilst the epiphyte coverage was correlated to the ice-ice incidence in K. alvarezii . This study provides the first evidence of biosecurity management measures significantly decreasing the incidence of the ice-ice syndrome and pests on a commercial seaweed farm.

Megadroughts and pluvials in southwest Australia: 1350–2017 CE - Alison J. O’Donnell; W. Lachlan McCaw; Edward R. Cook; Pauline F. Grierson (Climate Dynamics, 2021)
Declining winter rainfall coupled with recent prolonged drought poses significant risks to water resources and agriculture across southern Australia. While rainfall declines over recent decades are largely consistent with modelled climate change scenarios, particularly for southwest Australia, the significance of these declines is yet to be assessed within the context of long-term hydroclimatic variability. Here, we present a new 668-year (1350–2017 CE) tree-ring reconstruction of autumn–winter rainfall over inland southwest Australia. This record reveals that a recent decline in rainfall over inland southwest Australia (since 2000 CE) is not unusual in terms of either magnitude or duration relative to rainfall variability over the last seven centuries. Drought periods of greater magnitude and duration than those in the instrumental record occurred prior to 1900 CE, including two ‘megadroughts’ of > 30 years duration in the eighteenth and nineteenth centuries. By contrast, the wettest > decadal periods of the last seven centuries occurred after 1900 CE, making the twentieth century the wettest of the last seven centuries. We conclude that the instrumental rainfall record (since ~ 1900 CE) does not capture the full scale of natural hydroclimatic variability for inland southwest Australia and that the risk of prolonged droughts in the region is likely much higher than currently estimated.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Correction to: Biodiversity and Health in the Urban Environment - Melissa R. Marselle; Sarah J. Lindley; Penny A. Cook; Aletta Bonn (Current Environmental Health Reports, 2021)

Biodiversity and Health in the Urban Environment - Melissa R. Marselle; Sarah J. Lindley; Penny A. Cook; Aletta Bonn (Current Environmental Health Reports, 2021)
Purpose of review Biodiversity underpins urban ecosystem functions that are essential for human health and well-being. Understanding how biodiversity relates to human health is a developing frontier for science, policy and practice. This article describes the beneficial, as well as harmful, aspects of biodiversity to human health in urban environments. Recent findings Recent research shows that contact with biodiversity of natural environments within towns and cities can be both positive and negative to human physical, mental and social health and well-being. For example, while viruses or pollen can be seriously harmful to human health, biodiverse ecosystems can promote positive health and well-being. On balance, these influences are positive. As biodiversity is declining at an unprecedented rate, research suggests that its loss could threaten the quality of life of all humans. Summary A key research gap is to understand—and evidence—the specific causal pathways through which biodiversity affects human health. A mechanistic understanding of pathways linking biodiversity to human health can facilitate the application of nature-based solutions in public health and influence policy. Research integration as well as cross-sector urban policy and planning development should harness opportunities to better identify linkages between biodiversity, climate and human health. Given its importance for human health, urban biodiversity conservation should be considered as public health investment.

A 50-Year Retrospective of the Forest Productivity Cooperative in the Southeastern United States: Regionwide Trials - David R Carter; H Lee Allen; Thomas R Fox; Timothy J Albaugh; Rafael A Rubilar; Otávio C Campoe; Rachel L Cook (Journal of Forestry, 2021)
In 2019, the Forest Productivity Cooperative (FPC) celebrated its 50th anniversary. The mission of the FPC is and has been creating innovative solutions to enhance forest productivity and value through the sustainable management of site resources. This industry-government-university partnership has generated seminal research with sweeping implications for increasing productivity throughout the southeastern United States and Latin America. To commemorate this semicentennial, we highlighted some of the pivotal findings in the southeastern United States from the past 50 years derived from our large, regional experiments: regionwide trials.

A Multidisciplinary Approach to Investigate Deep-Pelagic Ecosystem Dynamics in the Gulf of Mexico Following Deepwater Horizon - April B. Cook; Andrea M. Bernard; Kevin M. Boswell; Heather Bracken-Grissom; Marta D’Elia; Sergio deRada; Cole G. Easson; David English; Ron I. Eytan; Tamara Frank; Chuanmin Hu; Matthew W. Johnston; et al. (Frontiers in Marine Science, 2020)
The pelagic Gulf of Mexico (GoM) is a complex system of dynamic physical oceanography (western boundary current, mesoscale eddies), high biological diversity, and community integration via diel vertical migration and lateral advection. Humans also heavily utilize this system, including its deep-sea components, for resource extraction, shipping, tourism, and other commercial activity. This utilization has had impacts, some with disastrous consequences. The Deepwater Horizon oil spill (DWHOS) occurred at a depth of ∼1500 m (Macondo wellhead), creating a persistent and toxic mixture of hydrocarbons and dispersant in the deep-pelagic (water column below 200 m depth) habitat. In order to assess the impacts of the DWHOS on this habitat, two large-scale research programs, described herein, were designed and executed. These programs, ONSAP and DEEPEND, aimed to quantitatively characterize the oceanic ecosystem of the northern GoM and to establish a time-series with which natural and anthropogenic changes could be detected. The approach was multi-disciplinary in nature and included in situ sampling, acoustic sensing, water column profiling and sampling, satellite remote sensing, AUV sensing, numerical modeling, genetic sequencing, and biogeochemical analyses. The synergy of these methodologies has provided new and unprecedented perspectives of an oceanic ecosystem with respect to composition, connectivity, drivers, and variability.

A little SNP of this, a little SNP of that: The discovery of 116 single nucleotide polymorphism markers to enable the rapid identification of individual Pacific walrus (Odobenus rosmarus divergens) - Geoffrey M. Cook; Daniel J. Prince; Sean M. O’Rourke; Timothy L. King; Michael R. Miller; Cara J. Lewis; Michael S. Eackles; Patrick R. Lemons; Suresh A. Sethi; Jeffrey B. Olsen; John K. Wenburg (Conservation Genetics Resources, 2020)

Low Static Shear Modulus Along Foliation and Its Influence on the Elastic and Strength Anisotropy of Poorman Schist Rocks, Homestake Mine, South Dakota - Katherine J. Condon; Hiroki Sone; Herbert F. Wang; J. Ajo-Franklin; T. Baumgartner; K. Beckers; D. Blankenship; A. Bonneville; L. Boyd; S. Brown; J. A. Burghardt; C. Chai; et al. (Rock Mechanics and Rock Engineering, 2020)

Racial and ethnic differences in risk of second primary cancers among prostate cancer survivors - Diana R. Withrow; Sara J. Schonfeld; Rochelle E. Curtis; Lindsay M. Morton; Michael B. Cook; Eboneé N. Butler; Amy Berrington de González (Cancer Causes & Control, 2020)

An analysis of the current status and future of biosecurity frameworks for the Indonesian seaweed industry - Cicilia S. B. Kambey; Iona Campbell; Calvyn F. A. Sondak; Adibi R. M. Nor; Phaik E. Lim; Elizabeth J. Cottier-Cook (Journal of Applied Phycology, 2020)
Indonesia is the world largest producer of the red seaweeds Kappaphycus and Eucheuma ; however, this country is facing significant challenges such as disease outbreaks, epiphyte infestations and a loss in seedling quality. Biosecurity practices have been widely adopted in other aquaculture sectors and when enforced can help to limit the introduction and spread of diseases and pests. To assess current capacity for biosecurity in seaweed aquaculture in Indonesia, a systematic analysis of policy frameworks including legislation, regulatory tools, and national standards was conducted. Biosecurity themes and risks were used to evaluate current national biosecurity content. The results identified major challenges faced by the industry in order to implement biosecurity policies in practice. Barriers to implementation included unspecific reference to the seaweed aquaculture sector, limited variety of approaches to biosecurity, limited use of up-to-date scientific evidence, insufficient guidance for the use of precaution and insufficient inclusion of specific biosecurity hazards. In general, although national regulations are currently under revision, current policies indicate a lack of clarity where biosecurity is included. Six recommendations are suggested to incorporate proactive biosecurity actions into current frameworks, with the aim of improving the health and sustainability of the seaweed aquaculture sector in Indonesia.

Correction to: Ancestral Folate Promotes Neuronal Regeneration in Serial Generations of Progeny - Nirav J. Patel; Kirk J. Hogan; Elias Rizk; Krista Stewart; Andy Madrid; Sivan Vadakkadath Meethal; Reid Alisch; Laura Borth; Ligia A. Papale; Solomon Ondoma; Logan R. Gorges; Kara Weber; et al. (Molecular Neurobiology, 2020)

Ancestral Folate Promotes Neuronal Regeneration in Serial Generations of Progeny - Nirav J. Patel; Kirk J. Hogan; Elias Rizk; Krista Stewart; Andy Madrid; Sivan Vadakkadath Meethal; Reid Alisch; Laura Borth; Ligia A. Papale; Solomon Ondoma; Logan R. Gorges; Kara Weber; et al. (Molecular Neurobiology, 2020)

Numerical modelling of rare earth element fractionation trends in garnet: a tool to monitor skarn evolution - Jing Xu; Cristiana L. Ciobanu; Nigel J. Cook; Youye Zheng; Xiaofeng Li; Benjamin P. Wade; Max R. Verdugo-Ihl; Wenyuan Gao; Qiaoqiao Zhu (Contributions to Mineralogy and Petrology, 2020)

Defining early stages of IOCG systems: evidence from iron oxides in the outer shell of the Olympic Dam deposit, South Australia - Max R. Verdugo-Ihl; Cristiana L. Ciobanu; Nigel J. Cook; Kathy J. Ehrig; Liam Courtney-Davies (Mineralium Deposita, 2020)

Crown architecture, crown leaf area distribution, and individual tree growth efficiency vary across site, genetic entry, and planting density - Timothy J. Albaugh; Chris A. Maier; Otávio C. Campoe; Marco A. Yáñez; Eric D. Carbaugh; David R. Carter; Rachel L. Cook; Rafael A. Rubilar; Thomas R. Fox (Trees, 2020)

Origin and age of The Hillocks and implications for post‐glacial landscape development in the upper Lake Wakatipu catchment, New Zealand - Samuel T. McColl; Simon J. Cook; Timothy Stahl; Timothy R. H. Davies (Journal of Quaternary Science, 2019)
Ambiguous landscape histories can arise from equivocal or incomplete geomorphological, sedimentological or geochronological evidence. In this study, we apply quantitative analyses to robustly assess the origin and age of a field of rounded mounds, known as ‘The Hillocks’. Using clast analysis, the sediment is shown to be consistent with a landslide origin but inconsistent with other glacial sediments in the region. Cosmogenic 10 Be exposure age dating suggests The Hillocks formed ~8 ka. Ground‐penetrating radar reveals that the deposit rests upon deltaic foreset beds; combined with topographical data, we calculate a deposit volume of ~15–27 M m 3 , consistent with the estimated volume of the proposed source area. Overall, our data support a rock avalanche origin, indicating that by 8 ka the valley was ice‐free at The Hillocks’ location, and the level of Lake Wakatipu was lower than 340 m asl by this time. The Dart River delta shoreline was situated somewhere between The Hillocks and the present day shoreline at that time, and has prograded at a maximum average rate of 1 m a −1 since ~8 ka. These findings are significant given the lack of landforms by which to constrain glacial or post‐glacial landscape histories in this region of New Zealand. Copyright © 2019 John Wiley & Sons, Ltd.

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

Toward the Integrated Marine Debris Observing System - Nikolai Maximenko; Paolo Corradi; Kara Lavender Law; Erik Van Sebille; Shungudzemwoyo P. Garaba; Richard Stephen Lampitt; Francois Galgani; Victor Martinez-Vicente; Lonneke Goddijn-Murphy; Joana Mira Veiga; Richard C. Thompson; Christophe Maes; et al. (Frontiers in Marine Science, 2019)

The state of Western Australia’s coral reefs - James P. Gilmour; Kylie L. Cook; Nicole M. Ryan; Marjetta L. Puotinen; Rebecca H. Green; George Shedrawi; Jean-Paul A. Hobbs; Damian P. Thomson; Russell C. Babcock; Joanna Buckee; Taryn Foster; Zoe T. Richards; et al. (Coral Reefs, 2019)

A Euro-Mediterranean tree-ring reconstruction of the winter NAO index since 910 C.E. - Edward R. Cook; Yochanan Kushnir; Jason E. Smerdon; A. Park Williams; Kevin J. Anchukaitis; Eugene R. Wahl (Climate Dynamics, 2019)

Tree-ring reconstructions of cool season temperature for far southeastern Australia, 1731–2007 - K. J. Allen; K. J. Anchukaitis; M. G. Grose; G. Lee; E. R. Cook; J. S. Risbey; T. J. O’Kane; D. Monselesan; A. O’Grady; S. Larsen; P. J. Baker (Climate Dynamics, 2019)

Implementation of a Systematic Tumor Screening Program for Lynch Syndrome in an Integrated Health Care Setting - Elizabeth V. Clarke; Kristin R. Muessig; Jamilyn Zepp; Jessica E. Hunter; Sapna Syngal; Louise S. Acheson; Georgia L. Wiesner; Susan K. Peterson; Kellene M. Bergen; Elizabeth Shuster; James V. Davis; Jennifer L. Schneider; et al. (Familial Cancer, 2019)

Forest Fertilizer Applications in the Southeastern United States from 1969 to 2016 - Timothy J Albaugh; Thomas R Fox; Rachel L Cook; Jay E Raymond; Rafael A Rubilar; Otávio C Campoe (Forest Science, 2019)

Cable bacteria promote DNRA through iron sulfide dissolution - Adam J. Kessler; Michaela Wawryk; Ugo Marzocchi; Keryn L. Roberts; Wei Wen Wong; Nils Risgaard‐Petersen; Filip J. R. Meysman; Ronnie N. Glud; Perran L. M. Cook (Limnology and Oceanography, 2019)
Cable bacteria represent a newly discovered group of filamentous microorganisms, which are capable of spatially separating the oxidative and reductive half‐reactions of their sulfide‐oxidizing metabolisms over centimeter distances. We investigated three ways that cable bacteria might interact with the nitrogen (N) cycle: (1) by reducing nitrate through denitrification or dissimilatory nitrate reduction to ammonium (DNRA) within their cathodic cells; (2) by nitrifying ammonium within their anodic cells; and (3) by indirectly affecting denitrification and/or DNRA by changing the Fe 2+ concentration in the surrounding sediment. We performed 15 N labeling laboratory experiments to measure these three processes using cable bacteria containing sediments from the Yarra River, Australia, and from Vilhelmsborg Sø, Denmark. Our results revealed that in the targeted systems, cable bacteria themselves did not perform significant rates of denitrification, DNRA, or nitrification. However, cable bacteria exhibited an important indirect effect, whereby they increased the Fe 2+ pool through iron sulfide dissolution. This elevated availability of Fe 2+ significantly increased DNRA and in some cases decreased denitrification. Thus, cable bacteria presence may affect the relative importance of DNRA in sediments and thus the extent by which bioavailable nitrogen is lost from the system.

How do climate change experiments alter plot‐scale climate? - A. K. Ettinger; I. Chuine; B. I. Cook; J. S. Dukes; A. M. Ellison; M. R. Johnston; A. M. Panetta; C. R. Rollinson; Y. Vitasse; E. M. Wolkovich (Ecology Letters, 2019)
To understand and forecast biological responses to climate change, scientists frequently use field experiments that alter temperature and precipitation. Climate manipulations can manifest in complex ways, however, challenging interpretations of biological responses. We reviewed publications to compile a database of daily plot‐scale climate data from 15 active‐warming experiments. We find that the common practices of analysing treatments as mean or categorical changes (e.g. warmed vs. unwarmed) masks important variation in treatment effects over space and time. Our synthesis showed that measured mean warming, in plots with the same target warming within a study, differed by up to 1.6 C (63% of target), on average, across six studies with blocked designs. Variation was high across sites and designs: for example, plots differed by 1.1 C (47% of target) on average, for infrared studies with feedback control ( n = 3) vs. by 2.2 C (80% of target) on average for infrared with constant wattage designs ( n = 2). Warming treatments produce non‐temperature effects as well, such as soil drying. The combination of these direct and indirect effects is complex and can have important biological consequences. With a case study of plant phenology across five experiments in our database, we show how accounting for drier soils with warming tripled the estimated sensitivity of budburst to temperature. We provide recommendations for future analyses, experimental design, and data sharing to improve our mechanistic understanding from climate change experiments, and thus their utility to accurately forecast species’ responses.

Training Needs of Clinical and Research Professionals to Optimize Minority Recruitment and Retention in Cancer Clinical Trials - Soumya J. Niranjan; Raegan W. Durant; Jennifer A. Wenzel; Elise D. Cook; Mona N. Fouad; Selwyn M. Vickers; Badrinath R. Konety; Sarah B. Rutland; Zachary R. Simoni; Michelle Y. Martin (Journal of Cancer Education, 2019)

Genome-wide association study of primary open-angle glaucoma in continental and admixed African populations - Pieter W. M. Bonnemaijer; Adriana I. Iglesias; Girish N. Nadkarni; Anna J. Sanyiwa; Hassan G. Hassan; Colin Cook; Mark Simcoe; Kent D. Taylor; Claudia Schurmann; Gillian M. Belbin; Eimear E. Kenny; Erwin P. Bottinger; et al. (Human Genetics, 2018)

Standardized reporting of the costs of management interventions for biodiversity conservation - Gwenllian D. Iacona; William J. Sutherland; Bonnie Mappin; Vanessa M. Adams; Paul R. Armsworth; Tim Coleshaw; Carly Cook; Ian Craigie; Lynn V. Dicks; James A. Fitzsimons; Jennifer McGowan; Andrew J. Plumptre; et al. (Conservation Biology, 2018)
Effective conservation management interventions must combat threats and deliver benefits at costs that can be achieved within limited budgets. Considerable effort has focused on measuring the potential benefits of conservation interventions, but explicit quantification of the financial costs of implementation is rare. Even when costs have been quantified, haphazard and inconsistent reporting means published values are difficult to interpret. This reporting deficiency hinders progress toward a collective understanding of the financial costs of management interventions across projects and thus limits the ability to identify efficient solutions to conservation problems or attract adequate funding. We devised a standardized approach to describing financial costs reported for conservation interventions. The standards call for researchers and practitioners to describe the objective and outcome, context and methods, and scale of costed interventions, and to state which categories of costs are included and the currency and date for reported costs. These standards aim to provide enough contextual information that readers and future users can interpret the cost data appropriately. We suggest these standards be adopted by major conservation organizations, conservation science institutions, and journals so that cost reporting is comparable among studies. This would support shared learning and enhance the ability to identify and perform cost‐effective conservation.

Trends of two HPV-associated cancers in Massachusetts: cervical and oropharyngeal cancer - Erin E. Cook; Susan T. Gershman; Jane J. Kim; Rulla M. Tamimi; R. Monina Klevens; Michelle D. Holmes (Cancer Causes & Control, 2018)

The role of catchment land use and tidal exchange in structuring estuarine fish assemblages - F. Y. Warry; P. Reich; P. L. M. Cook; R. Mac Nally; R. J. Woodland (Hydrobiologia, 2018)

Agro-morphological traits of Cicer reticulatum Ladizinsky in comparison to C. echinospermum P.H. Davis in terms of potential to improve cultivated chickpea (C. arietinum L.) - Mirlan Talip; Alper Adak; Abdullah Kahraman; Jens Berger; Duygu Sari; Hatice Sari; R. V. Penmetsa; E. J. von Wettberg; D. R. Cook; Cengiz Toker (Genetic Resources and Crop Evolution, 2018)

Advances in Silviculture of Intensively Managed Plantations - Rafael A. Rubilar; H. Lee Allen; Thomas R. Fox; Rachel L. Cook; Timothy J. Albaugh; Otávio C. Campoe (Current Forestry Reports, 2018)

First identification and characterization of Borrobol‐type tephra in the Greenland ice cores: new deposits and improved age estimates - Eliza Cook; Siwan M. Davies; Esther R. Guðmundsdóttir; Peter M. Abbott; Nicholas J. G. Pearce (Journal of Quaternary Science, 2018)
Contiguous sampling of ice spanning key intervals of the deglaciation from the Greenland ice cores of NGRIP, GRIP and NEEM has revealed three new silicic cryptotephra deposits that are geochemically similar to the well‐known Borrobol Tephra (BT). The BT is complex and confounded by the younger closely timed and compositionally similar Penifiler Tephra (PT). Two of the deposits found in the ice are in Greenland Interstadial 1e (GI‐1e) and an older deposit is found in Greenland Stadial 2.1 (GS‐2.1). Until now, the BT was confined to GI‐1‐equivalent lacustrine sequences in the British Isles, Sweden and Germany, and our discovery in Greenland ice extends its distribution and geochemical composition. However, the two cryptotephras that fall within GI‐1e ice cannot be separated on the basis of geochemistry and are dated to 14358 ± 177 a b2k and 14252 ± 173 a b2k, just 106 ± 3 years apart. The older deposit is consistent with BT age estimates derived from Scottish sites, while the younger deposit overlaps with both BT and PT age estimates. We suggest that either the BT in Northern European terrestrial sequences represents an amalgamation of tephra from both of the GI‐1e events identified in the ice‐cores or that it relates to just one of the ice‐core events. A firm correlation cannot be established at present due to their strong geochemical similarities. The older tephra horizon, found within all three ice‐cores and dated to 17326 ± 319 a b2k, can be correlated to a known layer within marine sediment cores from the North Iceland Shelf (ca. 17179‐16754 cal a BP). Despite showing similarities to the BT, this deposit can be distinguished on the basis of lower CaO and TiO 2 and is a valuable new tie‐point that could eventually be used in high‐resolution marine records to compare the climate signals from the ocean and atmosphere.

Expansion of landscape characterisation methods within the Hydrogeological Landscape Framework: application in the Australian Capital Territory - A. L. Cowood; C. L. Moore; M. J. Cracknell; J. Young; R. Muller; A. T. Nicholson; A. C. Wooldridge; B. R. Jenkins; W. Cook (Australian Journal of Earth Sciences, 2017)

Field-based assessment of wetland condition, wetland extent, and the National Wetlands Inventory in Kentucky, USA - Michelle Guidugli-Cook; Stephen C. Richter; Barbara J. Scott; David R. Brown (Wetlands Ecology and Management, 2017)

Influence of oceanographic conditions on abundance and distribution of post‐larval and juvenile carangid fishes in the northern Gulf of Mexico - John A. Mohan; Tracey T. Sutton; April B. Cook; Kevin M. Boswell; R. J. David Wells (Fisheries Oceanography, 2017)
Relationships between abundance of post‐larval and juvenile carangid (jacks) fishes and physical oceanographic conditions were examined in the northern Gulf of Mexico (GoM) in 2011 with high freshwater input from the Mississippi River. Generalized additive models ( GAM s) were used to explore complex relationships between carangid abundance and physical oceanographic data of sea surface temperature ( SST ), sea surface height anomaly ( SSHA ) and salinity. The five most abundant carangid species collected were: Selene setapinnis (34%); Caranx crysos (30%); Caranx hippos (10%); Chloroscombrus chrysurus (9%) and Trachurus lathami (8%). Post‐larval carangids (median standard length [ SL ] = 10 mm) were less abundant during the spring and early summer, but more abundant during the late summer and fall, suggesting summer to fall spawning for most species. Juvenile carangid (median SL = 23 mm) abundance also increased between the mid‐summer and early fall. Most species showed increased abundance at lower salinities and higher temperatures, suggesting entrainment of post‐larval fishes or feeding aggregations of juveniles at frontal convergence zones between the expansive river plume and dynamic mesoscale eddy water masses. However, responses were species‐ and life‐stage specific, which may indicate fine‐scale habitat partitioning between species. Ordination methods also revealed higher carangid abundances at lower salinities for both post‐larval and juvenile life stages, with species‐ and life‐stage specific responses to SST and SSHA , further suggesting habitat separation between species. Results indicate strong links between physical oceanographic features and carangid distributions in the dynamic northern GoM.

Universal screening for Lynch syndrome among patients with colorectal cancer: patient perspectives on screening and sharing results with at-risk relatives - Jessica Ezzell Hunter; Kathleen A. Arnold; Jennifer E. Cook; Jamilyn Zepp; Marian J. Gilmore; Alan F. Rope; James V. Davis; Kellene M. Bergen; Elizabeth Esterberg; Kristin R. Muessig; Susan K. Peterson; Sapna Syngal; et al. (Familial Cancer, 2017)

Spatial reconstruction of Scottish summer temperatures from tree rings - Miloš Rydval; Björn E. Gunnarson; Neil J. Loader; Edward R. Cook; Daniel L. Druckenbrod; Rob Wilson (International Journal of Climatology, 2017)
A detailed understanding of past temporal patterns and spatial expression of temperature variations is important to place recent anthropogenic climate change into a longer term context. In order to fill the current gap in our understanding of northwest European temperature variability, point‐by‐point principal component regression was used to reconstruct a spatial field of 0.5° temperature grids across Scotland. A sequence of reconstructions utilizing several combinations of detrending and disturbance correction procedures, and a selection of tree‐ring parameters [including ring width ( RW ), maximum latewood density ( MXD ) and blue intensity ( BI )] was used in an evaluation of reconstruction skill. The high resolution of the reconstructed field serves also as a diagnostic tool to spatially assess the temperature reconstruction potential of local chronologies. Best reconstruction results, reaching calibration r 2 = 65.8% and verification r 2 = 63.7% in central Scotland over the 1901–1976 period, were achieved using disturbance‐corrected and signal‐free detrended RW chronologies merged with BI data after low‐pass (high‐pass) filtering the RW ( BI ) chronologies. Calibration and verification r 2 > 50% was attained for central, north and east Scotland, >40% in west and northwest, and >30% in southern Scotland with verification of nearly all grids showing some reconstruction skill. However, the full calibration potential of reconstructions outside central Scotland was reduced either due to residual disturbance trends undetected by the disturbance correction procedure or due to other climatic or non‐climatic factors which may have adversely affected the strength of the climate signal.

Cape cormorants decrease, move east and adapt foraging strategies following eastward displacement of their main prey - RJM Crawford; RM Randall; TR Cook; PG Ryan; BM Dyer; R Fox; D Geldenhuys; J Huisamen; C McGeorge; MK Smith; L Upfold; J Visagie; et al. (African Journal of Marine Science, 2016)

Identifying the physical features of marina infrastructure associated with the presence of non-native species in the UK - Victoria Foster; Rebecca J. Giesler; A. Meriwether W. Wilson; Christopher R. Nall; Elizabeth J. Cook (Marine Biology, 2016)

Assessing the genetic architecture of epithelial ovarian cancer histological subtypes - Gabriel Cuellar-Partida; Yi Lu; Suzanne C. Dixon; Peter A. Fasching; Alexander Hein; Stefanie Burghaus; Matthias W. Beckmann; Diether Lambrechts; Els Van Nieuwenhuysen; Ignace Vergote; Adriaan Vanderstichele; Jennifer Anne Doherty; et al. (Human Genetics, 2016)

Development and characterization of a synthetic infectious cDNA clone of the virulent Bucyrus strain of equine arteritis virus expressing mCherry (red fluorescent protein) - Shankar P. Mondal; R. Frank Cook; R. Lakshman Chelvarajan; Pamela J. Henney; Peter J. Timoney; Udeni B. R. Balasuriya (Archives of Virology, 2016)

Deep dynamic pools of phosphorus in the sediment of a temperate lagoon with recurring blooms of diazotrophic cyanobacteria - Todd R. Scicluna; Ryan J. Woodland; Yafei Zhu; Michael R. Grace; Perran L. M. Cook (Limnology and Oceanography, 2015)
The storage and release of phosphorus by sediments can act as an important control on the formation of noxious blooms of cyanobacteria in lakes and estuaries. Here we studied the uptake and release of phosphorus associated with iron oxides within sediments of a lagoon system affected by recurring summer blooms of the cyanobacterium Nodularia spumigena . Using an ascorbate extraction, we observed deep pools of iron oxide associated phosphorus (P) at concentrations of ∼5 μ mol g −1 dry sed to a depth of ∼20 cm. This pool rapidly decreased with the onset of water column anoxia, leading to an integrated release of ∼300 mmol of phosphorus m −2 of sediment over 3.5 months. Scaling this flux over the periodically anoxic area of the lake and over the period of an N. spumigena bloom (November–December 2011) gave a broad mass balance agreement with the increase in total phosphorus within the water column and exported from the lagoon. Over this period we estimated that P release from the sediment would have allowed ∼130–187 tonnes of nitrogen to be fixed which agrees with previous estimates of nitrogen fixation. Upon reoxygenation of the water column, a regeneration of the deep iron oxide associated phosphorus pool was observed. This deep dynamic pool of phosphorus was most likely mediated by the burrowing activity of the polychaete Capitella capitata which was observed at the study site. This study underscores the potential importance of sediments colonized by deeply irrigating fauna to become a significant source of phosphorus during water column anoxia.

Nitrogen loads explain primary productivity in estuaries at the ecosystem scale - Ryan J. Woodland; James R. Thomson; Ralph Mac Nally; Paul Reich; Victor Evrard; Fiona Y. Wary; Jeffrey P. Walker; Perran L. M. Cook (Limnology and Oceanography, 2015)
Increased nutrient loads stimulate estuary primary productivity and can alter the structure and function of biological communities within estuaries, particularly when producer groups respond differently to changes in nutrient availability. Here, the relative influence of riverine inputs of nitrogen and phosphorus were compared to determine their contribution to estuarine primary producers at large spatial scales. Indices of demersal (extent of macroalgae relative to other vegetation, total shallow water area vegetated) and planktonic (seasonally averaged chlorophyll concentration) primary producer communities were derived at whole‐of‐ecosystem scales in 14 estuaries dispersed across a longitudinal gradient using aerial imaging, underwater videography and in situ monitoring. A model selection framework was used to relate annual nutrient loads (total nitrogen [TN], dissolved inorganic nitrogen [DIN], total phosphorus [TP]), sediment loads (TSS), molar stoichiometric load ratios (TN M : TP M ), and estuary water residence times to the demersal and planktonic indices. Dissolved inorganic nitrogen was the best predictor of the extent of macroalgae, total vegetation coverage, and the concentration of planktonic chlorophyll. Rapid increases in all three indices occurred at inorganic nitrogen loads of ∼ 5–10 Mg km −2 yr −1 . There was some evidence that TN M : TP M , TP and TSS loads were informative model covariates. Relative to DIN loads, TP loads were a poor predictor of the macroalgal and planktonic indices. These findings underscore the critical role of catchment‐derived nitrogen in contributing to producer communities at the whole‐of‐ecosystem scale and support the growing consensus that nitrogen loads (in addition to phosphorus) must be managed to effectively alleviate eutrophication in estuaries.

Evidence of climate‐driven ecosystem reorganization in the Gulf of Mexico - Mandy Karnauskas; Michael J. Schirripa; J. K. Craig; Geoffrey S. Cook; Christopher R. Kelble; Juan J. Agar; Bryan A. Black; David B. Enfield; David Lindo‐Atichati; Barbara A. Muhling; Kevin M. Purcell; Paul M. Richards; et al. (Global Change Biology, 2015)
The Gulf of Mexico is one of the most ecologically and economically valuable marine ecosystems in the world and is affected by a variety of natural and anthropogenic phenomena including climate, hurricanes, coastal development, agricultural runoff, oil spills, and fishing. These complex and interacting stressors, together with the highly dynamic nature of this ecosystem, present challenges for the effective management of its resources. We analyze a compilation of over 100 indicators representing physical, biological, and economic aspects of the Gulf of Mexico and find that an ecosystem‐wide reorganization occurred in the mid‐1990s. Further analysis of fishery landings composition data indicates a major shift in the late 1970s coincident with the advent of US national fisheries management policy, as well as significant shifts in the mid‐1960s and the mid‐1990s. These latter shifts are aligned temporally with changes in a major climate mode in the Atlantic Ocean: the Atlantic Multidecadal Oscillation ( AMO ). We provide an explanation for how the AMO may drive physical changes in the Gulf of Mexico, thus altering higher‐level ecosystem dynamics. The hypotheses presented here should provide focus for further targeted studies, particularly in regard to whether and how management should adjust to different climate regimes or states of nature. Our study highlights the challenges in understanding the effects of climatic drivers against a background of multiple anthropogenic pressures, particularly in a system where these forces interact in complex and nonlinear ways.

Quantifying the effects of light intensity on bioproduction and maintenance energy during photosynthetic growth of Rhodobacter sphaeroides - Saheed Imam; Colin M. Fitzgerald; Emily M. Cook; Timothy J. Donohue; Daniel R. Noguera (Photosynthesis Research, 2015)

Sex differences in ventricular–vascular coupling following endurance training - A. D. Lane; H. Yan; S. M. Ranadive; R. M. Kappus; P. Sun; M. D. Cook; I. Harvey; J. Woods; K. Wilund; B. Fernhall (European Journal of Applied Physiology, 2014)

Genome-wide association study of subtype-specific epithelial ovarian cancer risk alleles using pooled DNA - Madalene A. Earp; Linda E. Kelemen; Anthony M. Magliocco; Kenneth D. Swenerton; Georgia Chenevix-Trench; Yi Lu; Alexander Hein; Arif B. Ekici; Matthias W. Beckmann; Peter A. Fasching; Diether Lambrechts; Evelyn Despierre; et al. (Human Genetics, 2014)

Turning passive detection systems into field experiments: an application using wetland fishes and enclosures to track fine-scale movement and habitat choice - J. S. Rehage; R. E. Boucek; E. A. Cline; M. I. Cook; R. M. Kobza; A. K. Saha (acta ethologica, 2014)

Genome-wide association study of endometrial cancer in E2C2 - Immaculata De Vivo; Jennifer Prescott; Veronica Wendy Setiawan; Sara H. Olson; Nicolas Wentzensen; John Attia; Amanda Black; Louise Brinton; Chu Chen; Constance Chen; Linda S. Cook; Marta Crous-Bou; et al. (Human Genetics, 2014)

Antiretroviral drugs induce oxidative stress and neuronal damage in the central nervous system - Cagla Akay; Michael Cooper; Akinleye Odeleye; Brigid K. Jensen; Michael G. White; Fair Vassoler; Patrick J. Gannon; Joseph Mankowski; Jamie L. Dorsey; Alison M. Buch; Stephanie A. Cross; Denise R. Cook; et al. (Journal of NeuroVirology, 2014)
HIV-associated neurocognitive disorder (HAND), characterized by a wide spectrum of behavioral, cognitive, and motor dysfunctions, continues to affect approximately 50 % of HIV(+) patients despite the success of combination antiretroviral drug therapy (cART) in the periphery. Of note, potential toxicity of antiretroviral drugs in the central nervous system (CNS) remains remarkably underexplored and may contribute to the persistence of HAND in the cART era. Previous studies have shown antiretrovirals (ARVs) to be neurotoxic in the peripheral nervous system in vivo and in peripheral neurons in vitro. Alterations in lipid and protein metabolism, mitochondrial damage, and oxidative stress all play a role in peripheral ARV neurotoxicity. We hypothesized that ARVs also induce cellular stresses in the CNS, ultimately leading to neuronal damage and contributing to the changing clinical and pathological picture seen in HIV-positive patients in the cART era. In this report, we show that ARVs are neurotoxic in the CNS in both pigtail macaques and rats in vivo. Furthermore, in vitro, ARVs lead to accumulation of reactive oxygen species (ROS), and ultimately induction of neuronal damage and death. Whereas ARVs alone caused some activation of the endogenous antioxidant response in vitro, augmentation of this response by a fumaric acid ester, monomethyl fumarate (MMF), blocked ARV-induced ROS generation, and neuronal damage/death. These findings implicate oxidative stress as a contributor to the underlying mechanisms of ARV-induced neurotoxicity and will provide an access point for adjunctive therapies to complement ARV therapy and reduce neurotoxicity in this patient population.

Genetic diversity and complementary sex determination (CSD) in Dolerus aeneus (Hymenoptera, Symphyta): implications for the conservation of an ecologically-important sawfly - N. Cook; S. F. Hubbard; A. J. Karley; J. R. Russell (Conservation Genetics, 2013)

Tree-ring reconstructed summer temperature anomalies for temperate East Asia since 800 C.E. - Edward R. Cook; Paul J. Krusic; Kevin J. Anchukaitis; Brendan M. Buckley; Takeshi Nakatsuka; Masaki Sano (Climate Dynamics, 2013)

Estimating the Cost and Carbon Impact of a Long Term Water Main Rehabilitation Strategy - D. J. Beale; D. R. Marlow; S. Cook (Water Resources Management, 2013)

An improved solution for the infiltration advance problem in irrigation hydraulics - F. J. Cook; J. H. Knight; R. C. Doble; S. R. Raine (Irrigation Science, 2013)

A revised look: EPA rulemaking processes - Jeffrey J. Cook; Sara R. Rinfret (Journal of Environmental Studies and Sciences, 2013)

On the influence of tree size on the climate–growth relationship of New Zealand kauri (Agathis australis): insights from annual, monthly and daily growth patterns - Jan Wunder; Anthony M. Fowler; Edward R. Cook; Maryann Pirie; Shane P. J. McCloskey (Trees, 2013)

A strong regional temperature signal in low‐elevation Huon pine - K. J. ALLEN; D. M. DREW; G. M. DOWNES; R. EVANS; E. R. COOK; M. BATTAGLIA; P. J. BAKER (Journal of Quaternary Science, 2013)
We have produced the first annually resolved, centennial‐length tree‐ring chronologies, based on tracheid radial diameter (TRD) and microfibril angle for south‐eastern Australia (SEA) from what would commonly be considered a dendroclimatically suboptimal site. The chronologies exhibit a strong regional temperature signal for the austral summer (nominally November–April) that extends across much of SEA. The strength and spatial extent of the temperature–TRD correlations surpass those between the iconic Tasmanian Mt Read ring‐width chronology and austral summer temperatures, and are more time‐stable. We demonstrate that the value of wood property chronologies for their ability to improve the both the quality and the quantity of highly climate‐sensitive series available for regional annual‐resolution climate reconstructions, in data‐sparse regions in Australasia and beyond, should be examined. In light of the ‘divergence debate’, the time‐stability of relationships with climate, relative to other tree‐ring proxies, also requires further investigation.

A comparison of culture-dependent and culture-independent techniques used to characterize bacterial communities on healthy and white plague-diseased corals of the Montastraea annularis species complex - G. M. Cook; J. P. Rothenberger; M. Sikaroodi; P. M. Gillevet; E. C. Peters; R. B. Jonas (Coral Reefs, 2013)

Alpine cushion plants inhibit the loss of phylogenetic diversity in severe environments - B. J. Butterfield; L. A. Cavieres; R. M. Callaway; B. J. Cook; Z. Kikvidze; C. J. Lortie; R. Michalet; F. I. Pugnaire; C. Schöb; S. Xiao; B. Zaitchek; F. Anthelme; et al. (Ecology Letters, 2013)
Biotic interactions can shape phylogenetic community structure (PCS). However, we do not know how the asymmetric effects of foundation species on communities extend to effects on PCS. We assessed PCS of alpine plant communities around the world, both within cushion plant foundation species and adjacent open ground, and compared the effects of foundation species and climate on alpha (within‐microsite), beta (between open and cushion) and gamma (open and cushion combined) PCS. In the open, alpha PCS shifted from highly related to distantly related with increasing potential productivity. However, we found no relationship between gamma PCS and climate, due to divergence in phylogenetic composition between cushion and open sub‐communities in severe environments, as demonstrated by increasing phylo‐beta diversity. Thus, foundation species functioned as micro‐refugia by facilitating less stress‐tolerant lineages in severe environments, erasing a global productivity – phylogenetic diversity relationship that would go undetected without accounting for this important biotic interaction.

Links between Indo-Pacific climate variability and drought in the Monsoon Asia Drought Atlas - Caroline C. Ummenhofer; Rosanne D. D’Arrigo; Kevin J. Anchukaitis; Brendan M. Buckley; Edward R. Cook (Climate Dynamics, 2013)

Amycolatopsis umgeniensis sp. nov., isolated from soil from the banks of the Umgeni River in South Africa - Gareth J. Everest; Marilize le Roes-Hill; Clifford Omorogie; Shuk-Kwan Cheung; Andrew E. Cook; Candice M. Goodwin; Paul R. Meyers (Antonie van Leeuwenhoek, 2013)

A high-throughput SNP marker system for parental polymorphism screening, and diversity analysis in common bean (Phaseolus vulgaris L.) - Matthew W. Blair; Andrés J. Cortés; R. Varma Penmetsa; Andrew Farmer; Noelia Carrasquilla-Garcia; Doug R. Cook (Theoretical and Applied Genetics, 2013)

Sensitivity of Spring Phenology to Warming Across Temporal and Spatial Climate Gradients in Two Independent Databases - Benjamin I. Cook; Elizabeth M. Wolkovich; T. Jonathan Davies; Toby R. Ault; Julio L. Betancourt; Jenica M. Allen; Kjell Bolmgren; Elsa E. Cleland; Theresa M. Crimmins; Nathan J. B. Kraft; Lesley T. Lancaster; Susan J. Mazer; et al. (Ecosystems, 2012)

Parameter and uncertainty estimation for process‐oriented population and distribution models: data, statistics and the niche - Glenn Marion; Greg J. McInerny; Jörn Pagel; Stephen Catterall; Alex R. Cook; Florian Hartig; Robert B. O'Hara (Journal of Biogeography, 2012)
The spatial distribution of a species is determined by dynamic processes such as reproduction, mortality and dispersal. Conventional static species distribution models (SDMs) do not incorporate these processes explicitly. This limits their applicability, particularly for non‐equilibrium situations such as invasions or climate change. In this paper we show how dynamic SDMs can be formulated and fitted to data within a Bayesian framework. Our focus is on discrete state‐space Markov process models which provide a flexible framework to account for stochasticity in key demographic processes, including dispersal, growth and competition. We show how to construct likelihood functions for such models (both discrete and continuous time versions) and how these can be combined with suitable observation models to conduct Bayesian parameter inference using computational techniques such as Markov chain Monte Carlo. We illustrate the current state‐of‐the‐art with three contrasting examples using both simulated and empirical data. The use of simulated data allows the robustness of the methods to be tested with respect to deficiencies in both data and model. These examples show how mechanistic understanding of the processes that determine distribution and abundance can be combined with different sources of information at a range of spatial and temporal scales. Application of such techniques will enable more reliable inference and projections, e.g. under future climate change scenarios than is possible with purely correlative approaches. Conversely, confronting such process‐oriented niche models with abundance and distribution data will test current understanding and may ultimately feedback to improve underlying ecological theory.

Influences of the El Niño Southern Oscillation and the Pacific Decadal Oscillation on the timing of the North American spring - Gregory J. McCabe; Toby R. Ault; Benjamin I. Cook; Julio L. Betancourt; Mark D. Schwartz (International Journal of Climatology, 2012)
Detrended, modelled first leaf dates for 856 sites across North America for the period 1900–2008 are used to examine how the El Niño Southern Oscillation (ENSO) and the Pacific Decadal Oscillation (PDO) separately and together might influence the timing of spring. Although spring (mean March through April) ENSO and PDO signals are apparent in first leaf dates, the signals are not statistically significant (at a 95% confidence level ( p p

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Reconciling estimates of the contemporary North American carbon balance among terrestrial biosphere models, atmospheric inversions, and a new approach for estimating net ecosystem exchange from inventory‐based data - Daniel J. Hayes; David P. Turner; Graham Stinson; A. David McGuire; Yaxing Wei; Tristram O. West; Linda S. Heath; Bernardus de Jong; Brian G. McConkey; Richard A. Birdsey; Werner A. Kurz; Andrew R. Jacobson; et al. (Global Change Biology, 2012)
We develop an approach for estimating net ecosystem exchange ( NEE ) using inventory‐based information over North America ( NA ) for a recent 7‐year period (ca. 2000–2006). The approach notably retains information on the spatial distribution of NEE , or the vertical exchange between land and atmosphere of all non‐fossil fuel sources and sinks of CO 2 , while accounting for lateral transfers of forest and crop products as well as their eventual emissions. The total NEE estimate of a −327 ± 252 TgC yr −1 sink for NA was driven primarily by CO 2 uptake in the Forest Lands sector (−248 TgC yr −1 ), largely in the Northwest and Southeast regions of the US, and in the Crop Lands sector (−297 TgC yr −1 ), predominantly in the Midwest US states. These sinks are counteracted by the carbon source estimated for the Other Lands sector (+218 TgC yr −1 ), where much of the forest and crop products are assumed to be returned to the atmosphere (through livestock and human consumption). The ecosystems of Mexico are estimated to be a small net source (+18 TgC yr −1 ) due to land use change between 1993 and 2002. We compare these inventory‐based estimates with results from a suite of terrestrial biosphere and atmospheric inversion models, where the mean continental‐scale NEE estimate for each ensemble is −511 TgC yr −1 and −931 TgC yr −1 , respectively. In the modeling approaches, all sectors, including Other Lands, were generally estimated to be a carbon sink, driven in part by assumed CO 2 fertilization and/or lack of consideration of carbon sources from disturbances and product emissions. Additional fluxes not measured by the inventories, although highly uncertain, could add an additional −239 TgC yr −1 to the inventory‐based NA sink estimate, thus suggesting some convergence with the modeling approaches.

Sources and fate of nutrients in a subtropical reservoir - Michele A. Burford; Susanne A. Green; Andrew J. Cook; Suzanne A. Johnson; Jason G. Kerr; Katherine R. O’Brien (Aquatic Sciences, 2012)

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

The potential to reconstruct broadscale climate indices associated with southeast Australian droughts from Athrotaxis species, Tasmania - K. J. Allen; J. Ogden; B. M. Buckley; E. R. Cook; P. J. Baker (Climate Dynamics, 2011)

Evaluation of the use of recN sequence analysis in the phylogeny of the genus Amycolatopsis - Gareth J. Everest; Andrew E. Cook; Bronwyn M. Kirby; Paul R. Meyers (Antonie van Leeuwenhoek, 2011)

Problematic but promising ponds? Palaeoenvironmental evidence from the Norse Eastern Settlement of Greenland - Kevin J. Edwards; J. Edward Schofield; Jason R. Kirby; Gordon T. Cook (Journal of Quaternary Science, 2011)
Pollen‐ and related proxy‐based studies of human–environment interactions during the Norse and later periods within Greenland have primarily involved the investigation of peat, lake and soil deposits, all of which have taphonomic and sampling problems. Many small ponds exist, but they seem to have been relatively ignored in investigations of palaeoecologically based environmental history. To evaluate their usefulness for studies of ecologically related cultural history, especially where sites are in intimate association with the archaeology, a pond in the Norse Eastern Settlement has been examined to investigate three principal questions: (i) Does such a site contain a useful record of environmental history? (ii) Does it offer a record of sufficient resolution and sensitivity for the study of anthropogenic landscape impacts? (iii) Are there any apparent drawbacks to these sequences? Using data obtained from palynological, diatom, sedimentological and radiocarbon analyses, it is concluded that environmental data for each proxy – aside from 14 C dating – are clearly capable of being explained in a reasonably straightforward and compatible manner and fulfil the hopes for the sampling medium. Copyright © 2011 John Wiley & Sons, Ltd.

Transcriptome sequencing of an ecologically important graminivorous sawfly: a resource for marker development - N. Cook; N. Aziz; P. E. Hedley; J. Morris; L. Milne; A. J. Karley; S. F. Hubbard; J. R. Russell (Conservation Genetics Resources, 2011)

Forced and unforced variability of twentieth century North American droughts and pluvials - Benjamin I. Cook; Edward R. Cook; Kevin J. Anchukaitis; Richard Seager; Ron L. Miller (Climate Dynamics, 2011)

Repurposing climate reconstructions for drought prediction in Southeast Asia - Andrew R. Bell; Benjamin I. Cook; Kevin J. Anchukaitis; Brendan M. Buckley; Edward R. Cook (Climatic Change, 2011)

Factors limiting the health of semi-scavenging ducks in Bangladesh - M. A. Hoque; L. F. Skerratt; A. J. C. Cook; S. A. Khan; D. Grace; M. R. Alam; A. Vidal-Diez; N. C. Debnath (Tropical Animal Health and Production, 2011)

Biogeography of the Australian monsoon tropics - D. M. J. S. Bowman; G. K. Brown; M. F. Braby; J. R. Brown; L. G. Cook; M. D. Crisp; F. Ford; S. Haberle; J. Hughes; Y. Isagi; L. Joseph; J. McBride; et al. (Journal of Biogeography, 2010)
Aim This paper reviews the biogeography of the Australian monsoon tropical biome to highlight general patterns in the distribution of a range of organisms and their environmental correlates and evolutionary history, as well as to identify knowledge gaps. Location Northern Australia, Australian Monsoon Tropics (AMT). The AMT is defined by areas that receive more than 85% of rainfall between November and April. Methods Literature is summarized, including the origin of the monsoon climate, present‐day environment, biota and habitat types, and phylogenetic and geographical relationships of selected organisms. Results Some species are widespread throughout the AMT while others are narrow‐range endemics. Such contrasting distributions correspond to present‐day climates, hydrologies (particularly floodplains), geological features (such as sandstone plateaux), fire regimes, and vegetation types (ranging from rain forest to savanna). Biogeographical and phylogenetic studies of terrestrial plants (e.g. eucalypts) and animals (vertebrates and invertebrates) suggest that distinct bioregions within the AMT reflect the aggregated effects of landscape and environmental history, although more research is required to determine and refine the boundaries of biogeographical zones within the AMT. Phylogenetic analyses of aquatic organisms (fishes and prawns) suggest histories of associations with drainage systems, dispersal barriers, links to New Guinea, and the existence of Lake Carpentaria, now submerged by the Gulf of Carpentaria. Complex adaptations to the landscape and climate in the AMT are illustrated by a number of species. Main conclusions The Australian monsoon is a component of a single global climate system, characterized by a dominant equator‐spanning Hadley cell. Evidence of hot, seasonally moist climates dates back to the Late Eocene, implying that certain endemic elements of the AMT biota have a long history. Vicariant differentiation is inferred to have separated the Kimberley and Arnhem Land bioregions from Cape York Peninsula/northern Queensland. Such older patterns are overlaid by younger events, including dispersal from Southeast Asia, and range expansions and contractions. Future palaeoecological and phylogenetic investigations will illuminate the evolution of the AMT biome. Understanding the biogeography of the AMT is essential to provide a framework for ecological studies and the sustainable development of the region.

The petrogenesis of sodic island arc magmas at Savo volcano, Solomon Islands - D. J. Smith; M. G. Petterson; A. D. Saunders; I. L. Millar; G. R. T. Jenkin; T. Toba; J. Naden; J. M. Cook (Contributions to Mineralogy and Petrology, 2009)

An Investigation into the Rheology of Pharmaceutical Inter-granular Material Bridges at High Shear Rates - Barry Crean; Xinyong Chen; Simon R. Banks; Walter G. Cook; Colin D. Melia; Clive J. Roberts (Pharmaceutical Research, 2009)

Steady Groundwater Flow to Drains on a Sloping Bed: Comparison of Solutions Based on Boussinesq Equation and Richards Equation - F. J. Cook; J. H. Knight; R. A. Wooding (Transport in Porous Media, 2009)

Electronic tags reveal behaviour of captured and discarded fish - F. C. Neat; M. Breen; R. M. Cook; I. M. Gibb; P. J. Wright (Journal of Fish Biology, 2009)
Internally implanted data storage tags (DST) recording hydrostatic pressure (depth) and temperature in Atlantic cod Gadus morhua were used to track the behaviour of nine individuals during fishing operations. Gadus morhua showed identifiable and characteristic behavioural responses to different capture processes. In a unique observation, one fish survived being discarded and upon return to the seabed exhibited a cessation of activity comparable to observations on stressed fish under laboratory conditions.

Resolving relationships in some African fungus-growing termites (Termitidae, Macrotermitinae) using molecular phylogeny, morphology, and field parameters - J. P. E. C. Darlington; R. B. Benson; C. E. Cook; G. Walker (Insectes Sociaux, 2008)

Using Light-Use and Production Efficiency Models to Predict Photosynthesis and Net Carbon Exchange During Forest Canopy Disturbance - Bruce D. Cook; Paul V. Bolstad; Jonathan G. Martin; Faith Ann Heinsch; Kenneth J. Davis; Weiguo Wang; Ankur R. Desai; Ron M. Teclaw (Ecosystems, 2008)

Relationship Between the Endophyte Embellisia spp. and the Toxic Alkaloid Swainsonine in Major Locoweed Species (Astragalus and Oxytropis) - M. H. Ralphs; R. Creamer; D. Baucom; D. R. Gardner; S. L. Welsh; J. D. Graham; C. Hart; D. Cook; B. L. Stegelmeier (Journal of Chemical Ecology, 2008)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Neurobehavioral mutants identified in an ENU-mutagenesis project - Melloni N. Cook; Jonathan P. Dunning; Ronald G. Wiley; Elissa J. Chesler; Dabney K. Johnson; Darla R. Miller; Dan Goldowitz (Mammalian Genome, 2007)

Soil–water and solute movement under precision irrigation: knowledge gaps for managing sustainable root zones - S. R. Raine; W. S. Meyer; D. W. Rassam; J. L. Hutson; F. J. Cook (Irrigation Science, 2007)

Thermal tolerance of a northern population of striped bass Morone saxatilis - A. M. Cook; J. Duston; R. G. Bradford (Journal of Fish Biology, 2006)
Thermal tolerance of age 0+ year Shubenacadie River (Nova Scotia, Canada) striped bass Morone saxatilis juveniles (mean ± s . e . fork length, L F , 19·2 ± 0·2 cm) acclimated in fresh water to six temperatures from 5 to 30° C was measured by both the incipient lethal technique (72 h assay), and the critical thermal method ( C m ). The lower incipient lethal temperature ranged from 2·4 to 11·3° C, and the upper incipient lethal temperature ( I U ) from 24·4 to 33·9° C. The area of thermal tolerance was 618° C 2 . In a separate experiment, the I U of large age 2+ year fish (34·4 ± 0·5 cm L F ) was 1·2 and 0·6° C lower ( P L F ) at acclimation temperatures of 16 and 23° C. Using the C m , loss of equilibrium occurred at 27·4–37·7° C, loss of righting response at 28·1–38·4° C and onset of spasms at 28·5–38·8° C, depending on acclimation temperature. The linear regression slopes for these three responses were statistically similar (0·41; P > 0·05), but the intercepts differed (25·3, 26·0 and 26·5° C; P

Millennia‐long tree‐ring records from Tasmania and New Zealand: a basis for modelling climate variability and forcing, past, present and future - Edward R. Cook; Brendan M. Buckley; Jonathan G. Palmer; Pavla Fenwick; Michael J. Peterson; Gretel Boswijk; Anthony Fowler (Journal of Quaternary Science, 2006)
Progress in the development of millennia‐long tree‐ring chronologies from Australia and New Zealand is reviewed from the perspective of modelling long‐term climate variability there. Three tree species have proved successful in this regard: Huon pine ( Lagarostrobos franklinii ) from Tasmania, silver pine ( L. colensoi ) from the South Island of New Zealand, and kauri ( Agathis australis ) from the North Island of New Zealand. Each of these species is very long‐lived and produces abundant quantities of well‐preserved wood for extending their tree‐ring chronologies back several millennia into the past. The growth patterns on these chronologies strongly correlate with both local and regional warm‐season temperature changes over significant areas of the Southern Hemisphere (especially Huon and silver pine) and to ENSO variability emanating from the equatorial Pacific region (especially kauri). In addition, there is evidence for significant, band‐limited, multi‐decadal and centennial timescale variability in the warm‐season temperature reconstruction based on Huon pine tree rings that may be related to slowly varying changes in ocean circulation dynamics in the southern Indian Ocean. This suggests the possibility of long‐term climate predictability there. Copyright © 2006 John Wiley & Sons, Ltd.

Rapid development of polyclonal antisera against infectious salmon anaemia virus and its optimization and application as a diagnostic tool - S J McBeath; L M Ellis; P F Cook; L Wilson; K L Urquhart; I R Bricknell (Journal of Fish Diseases, 2006)
Infectious salmon anaemia is an important disease of Atlantic salmon. One of the current methods of diagnosis is the indirect fluorescent antibody test (IFAT), using a monoclonal antibody specific to the haemagglutinin of the virus. The conformationally dependent nature of this antibody could be a drawback in its usefulness in other tests. This study describes the development and optimization of a polyclonal antiserum against infectious salmon anaemia virus, including a method of separating virus from cell culture components within culture supernatant. The antiserum was subsequently optimized for use in a variety of immunological diagnostic tests, including IFAT and an alkaline phosphatase‐based immunoassay, and Western blot.

Phylogenetics of New World Astragalus: Screening of novel nuclear loci for the reconstruction of phylogenies at low taxonomic levels - Rosa A. Scherson; Hong-Kyu Choi; Douglas R. Cook; Michael J. Sanderson (Brittonia, 2005)

Use of Simulated Annealing for Identifying Essential Fish Habitat in a Multispecies Context - ROSAMONDE R. COOK; PETER J. AUSTER (Conservation Biology, 2005)
Essential fish habitat (EFH) is defined under U.S. federal law, which mandates its protection. Current single‐species approaches to identifying EFH for suites of managed species have resulted in areas designated for protection that are so large that protecting fish habitat has been difficult in the context of fishery management. We evaluated the potential for simulated annealing, a type of mathematical optimization, as a tool for simultaneously identifying EFH for multiple species in four ecological regions of the eastern continental shelf of the United States. Data were obtained from a shelf‐wide trawl survey with site‐specific abundance information spanning 37 years. The data were averaged within units of a sampling grid with 10‐minute squares. We used computer software with an objective function that includes a term for weighting the boundary length of selected sampling units and thereby identifies solutions that meet specific targets for representation under varying degrees of spatial aggregation. We defined representation as a percentage of the cumulative sampled abundance of individual species and examined the effects of these target values and spatial constraints on total (sea‐surface) area and boundary length of solution sets. We also evaluated the algorithm for its ability to select areas where juveniles occurred at high densities as a proxy for habitat value. Annealing solutions covered less total area than would the combined habitats of individual species that capture the same proportion of population abundance. For most species in most solutions, high‐density areas were selected in higher proportions to their relative abundance in a region and solutions contained less total habitat area and smaller boundary lengths. Additionally, sampling units were distributed among two or more discrete localities versus a single location for the same target level of representation. We suggest that simulated annealing is a viable tool for EFH planning with the potential for identifying more spatially conservative habitat areas for protection than a single‐species approach.

Incubation reduces microbial growth on eggshells and the opportunity for trans‐shell infection - Mark I. Cook; Steven R. Beissinger; Gary A. Toranzos; Wayne J. Arendt (Ecology Letters, 2005)
Avian eggshells harbour microbes shortly after laying, and under appropriate ambient conditions they can multiply rapidly, penetrate through shell pores, infect egg contents and cause embryo mortality. We experimentally examined how incubation affects bacterial processes on the eggshells of pearl‐eyed thrashers Margarops fuscatus nesting in tropical montane and lowland forests in Puerto Rico. Bacteria and fungi grew rapidly on shells of newly laid, unincubated eggs exposed to ambient conditions, but declined to low levels on shells of eggs incubated by thrashers. Divergence in bacterial growth between incubated and exposed eggs was more marked at the montane forest than at the lowland site. Pathogenic microorganisms became increasingly dominant on shells of exposed eggs, but these groups were relatively rare on incubated eggs, where more benign, less invasive groups prevailed. Some incubation during laying may be necessary to decrease the probability of trans‐shell infection by reducing the growth of harmful bacteria and fungi on eggshells, although it may increase hatching asynchrony and the likelihood of brood reduction.

Different populations of RNA polymerase II in living mammalian cells - Miki Hieda; Henry Winstanley; Philip Maini; Francisco J. Iborra; Peter R. Cook (Chromosome Research, 2005)

Development of a micro-sward technique for determining intake characteristics of perennial ryegrass varieties - R. J. Orr; K. L. Young; J. E. Cook; R. A. Champion (Euphytica, 2005)

West Nile virus: pending crisis for greater sage‐grouse - David E. Naugle; Cameron L. Aldridge; Brett L. Walker; Todd E. Cornish; Brendan J. Moynahan; Matt J. Holloran; Kimberly Brown; Gregory D. Johnson; Edward T. Schmidtmann; Richard T. Mayer; Cecilia Y. Kato; Marc R. Matchett; et al. (Ecology Letters, 2004)
Scientists have feared that emerging infectious diseases could complicate efforts to conserve rare and endangered species, but quantifying impacts has proven difficult until now. We report unexpected impacts of West Nile virus (WNv) on radio‐marked greater sage‐grouse ( Centrocercus urophasianus ), a species that has declined 45–80% and is endangered in Canada and under current consideration for federal listing in the US. We show that WNv reduced late‐summer survival an average of 25% in four radio‐marked populations in the western US and Canada. Serum from 112 sage‐grouse collected after the outbreak show that none had antibodies, suggesting that they lack resistance. The spread of WNv represents a significant new stressor on sage‐grouse and probably other at‐risk species. While managing habitat might lessen its impact on sage‐grouse populations, WNv has left wildlife and public health officials scrambling to address surface water and vector control issues in western North America.

AZT inhibits Visna/maedi virus -induced apoptosis - V. Bellet; R. Duval; S. Delebasse; J. Cook-Moreau; C. Bosgiraud (Archives of Virology, 2004)

Influence of pasture management (nitrogen and lime addition and insecticide treatment) on soil organisms and pasture root system dynamics in the field - L. A. Dawson; S. J. Grayston; P. J. Murray; R. Cook; A. C. Gange; J. M. Ross; S. M. Pratt; E. I. Duff; A. Treonis (Plant and Soil, 2003)

Dendroclimatic signals in long tree‐ring chronologies from the Himalayas of Nepal - Edward R. Cook; Paul J. Krusic; Philip D. Jones (International Journal of Climatology, 2003)
We describe the development of a tree‐ring chronology network in Nepal that is suitable for reconstructing temperature‐related climate forcing over the past few hundred years. The network is composed of 32 tree‐ring chronologies and is represented by five indigenous tree species. An empirical orthogonal function analysis of the chronologies over the common interval 1796–92 indicates the existence of coherent large‐scale signals among the tree‐ring chronologies that are hypothesized to reflect, in part, broad‐scale climate forcing related to temperatures. A long monthly temperature record for Kathmandu is developed and used to test this hypothesis. In so doing, significant monthly and seasonal temperature responses are identified that provide guidance for the formal reconstruction of two temperature seasons: February–June (1546–91) and October–February (1605–91). Each reconstruction indicates the occurrence of unusually cold temperatures in 1815–22, which coincides with the eruption of Tambora in Indonesia. A novel method is also used to add probable missing multi‐centennial temperature variance to each reconstruction. The resulting ‘adjusted’ reconstructions strongly reflect patterns of temperature variability associated with Little Ice Age cooling and warming into the 20th century, with the October–February season exhibiting the strongest increase in temperature over the past ∼400 years. Only the October–February season shows any evidence for late‐ 20th century warming, whereas February–June temperatures have actually cooled since 1960 (as with the observational series). Copyright © 2003 Royal Meteorological Society

An Integrated Pharmacodynamic Analysis of Erythropoietin, Reticulocyte, and Hemoglobin Responses in Acute Anemia - P. Veng-Pederson; S. Chapel; P. R. L. Schmidt; N. H. Al-Huniti; R. T. Cook; J. A. Widness (Pharmaceutical Research, 2002)

An alkaline phosphatase‐based method for the detection of infectious salmon anaemia virus (ISAV) in tissue culture and tissue imprints - L Wilson; S J McBeath; K L Adamson; P F Cook; L M Ellis; I R Bricknell (Journal of Fish Diseases, 2002)
Currently, the presence of infectious salmon anaemia virus (ISAV) is often detected in Atlantic salmon by the use of an indirect fluorescent antibody test. This test is limited by the poor stability of fluorescein isothiocyanate which fades after about a week in storage, preventing the development of stained archive material as a reference source. One possible alternative would be the use of immunohistochemical staining methods to detect ISAV. An immunohistochemical method is presented that uses alkaline phosphatase‐conjugated antibodies and Vector ® Red as a substrate, to detect ISAV in kidney imprints. This paper also describes a procedure where Bouin's fluid is used to successfully inhibit endogenous alkaline phosphatase in tissue samples, prior to immunohistochemical processing. This method provides a stable stain that can be read for many weeks after staining or archived for future reference.

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. VII. Overview and discussion - I. W. B. Thornton; S. Cook; J. S. Edwards; R. D. Harrison; C. Schipper; M. Shanahan; R. Singadan; R. Yamuna (Journal of Biogeography, 2001)
Location, aims Long Island's biota was destroyed by volcanic eruption in c. 1645, and Motmot, an emergent island in its caldera lake, was re‐created in 1968, providing a nested pair of natural colonization sequences. In 1999 we surveyed the plants and vertebrates of Long and the entire biota of Motmot for comparison with previous surveys of Long (1932, 1972, birds only) and Motmot (1969–88). Results The known flora of Long is 305 vascular plants (thirty‐two pteridophytes, 273 spermatophytes), including thirty‐one Ficus species, the sixteen fruiting all having pollinating wasps, and there were eleven species of effective fig dispersers. There were two frog species, a crocodile, a monitor, seven skinks, four geckos, a boid snake, fifty species non‐migrant land birds, seven bats, two rats, a cuscus (probably introduced) and feral pigs, dogs, cats and chickens. Most of Motmot's surface was barren or sparsely vegetated ash, cinder and lava fields. There were seven pteridophyte and thirty‐eight spermatophyte species, including eight Ficus , and the cumulative known flora comprises eleven pteridophytes and fifty‐one spermatophytes, mainly zoochorous and anemochorous, with sedges, grasses and herbs predominating. All Ficus individuals but one were small; three plants of two species bore syconia but had not been pollinated and had not set seed. Motmot's known invertebrate fauna comprises thirty‐five species, mainly predators and scavengers; two spider and one ant species dominating. An insectivorous bat and eight land bird species (three breeding) were the only vertebrates. Main conclusions Long's biota comprised mainly widely distributed species with broad ecological tolerances, well‐adapted for colonizing species‐poor islands. The mid‐level caldera plateau, as in 1932, was covered in fairly open forest of similar‐sized trees with a few much larger individuals and little or no understorey. Primary rain forest tree species from the region were under‐represented or absent but secondary forest species were common. There were few regional endemic Ficus species. The avifauna comprised species with good dispersal ability, lacked endemic subspecies and probably for at least the past seven decades has been held at a quasi‐equilibrium of fifty species, fourteen below the theoretical number. More than half the fifty‐four resident land birds known from Long (and three of the seven bats) are high class tramps in the sense of Diamond; only two birds are high‐S species. Turnover has been low and none of the bird super tramps has been replaced. The non‐avian fauna comprised mostly high‐category tramptype species with relatively broad habitat requirements and extensive geographical ranges. Non‐volant vertebrates comprised a number of highly vagile species associated with humans. Several groups, especially snakes and amphibians, were depauperate compared with the fauna of other islands in the area. Long's biota is evidently held at an arrested stage of development by some physical factor, possibly the extremely porous substratum and relatively dry climate. The allochthonous input of lake insects to Motmot evidently provides the major energy source for its animal communities, with a very minor contribution from organic flotsam. Reflecting Motmot's very isolated situation, plant colonization has been slow, but when more fig individuals mature and fig–wasp populations become established fruit production should attract frugivores and start a positive feedback process which will accelerate the growth of Motmot's community. Long's colonization shows similarities with that of Krakatau (Sunda Strait, Indonesia) after the 1883 eruption, and species shared by the two include a high proportion of pioneer species. Motmot's triple isolation (sea, land and fresh‐water barriers) means that its colonization differs markedly from those on two marine emergent islands of the region, Tuluman (Admiralty Group) and Anak Krakatau.

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. VII. Overview and discussion - I. W. B. Thornton; S. Cook; J. S. Edwards; R. D. Harrison; C. Schipper; M. Shanahan; R. Singadan; R. Yamuna (Journal of Biogeography, 2001)

The climatic response of Phyllocladus aspleniifolius (Labill.) Hook. f in Tasmania - K. J. Allen; E. R. Cook; R. J. Francey; K. Michael (Journal of Biogeography, 2001)
Aim To examine the response of ring widths of Phyllocladus aspleniifolius to maximum and minimum temperatures and to a zonal index (ZI). Location Tasmania, Australia. Methods Between two and four increment cores were obtained from approximately 20 trees at each of 16 sites of P. aspleniifolius across Tasmania. Four regions were defined and temperature data for climate stations from each of these regions were transformed into dimensionless time series appropriate for each region. The ZI was constructed from Melbourne and Hobart mean sea level pressure (MSLP). Correlations were calculated between climate data and ring widths over most of the 20th century. Data were then segregated into two subperiods to assess whether or not temporal changes in ring width response have occurred over the 20th century. Results The dominant feature of the correlation functions was a negative correlation with temperatures of the previous growing season. Correlation between the ZI and ring width is most significant, and positive, in November and March of the previous growing season. Differences in the shape of the correlation functions, and their strength is apparent over the course of the century. In general, correlations have become weaker and less consistent among the 16 sites for the latter part of the century. Temperatures have generally increased during the 1900s over which time period correlations have been calculated. Main conclusions The temporally changing climatic response in ring widths is consistent with a hypothesis of competition for resources between different parts of a plant. A nonlinear response to climate over a short‐time period violates one of the basic assumptions of dendroclimatology, therefore suggesting further investigation of both the physiology of trees used for dendroclimatological purposes and the statistical methods used for climatic reconstruction.

Trans-Tasman Sea climate variability since ad 1740 inferred from middle to high latitude tree-ring data - R. D'Arrigo; E. Cook; R. Villalba; B. Buckley; J. Salinger; J. Palmer; K. Allen (Climate Dynamics, 2000)

Sex-related differences in the antinociceptive effects of opioids: importance of rat genotype, nociceptive stimulus intensity, and efficacy at the µ opioid receptor - Charles D. Cook; Andrew C. Barrett; Emily L. Roach; Joseph R. Bowman; Mitchell J. Picker (Psychopharmacology, 2000)

Warm-season temperatures since 1600 BC reconstructed from Tasmanian tree rings and their relationship to large-scale sea surface temperature anomalies - E. R. Cook; B. M. Buckley; R. D. D'Arrigo; M. J. Peterson (Climate Dynamics, 2000)

Bay‐scale population structure in coastal Atlantic cod in Labrador and Newfoundland, Canada - D. E. Ruzzante; J. S. Wroblewski; C. T. Taggart; R. K. Smedbol; D. Cook; S. V. Goddaard (Journal of Fish Biology, 2000)
Polymorphisms at five microsatellite DNA loci provide evidence that Atlantic cod Gadus morhua inhabiting Gilbert Bay, Labrador are genetically distinguishable from offshore cod on the north‐east Newfoundland shelf and from inshore cod in Trinity Bay, Newfoundland. Antifreeze activity in the blood suggests that Gilbert Bay cod overwinter within the Bay. Gilbert Bay cod are also smaller (weight and length) for their age and consequently less fecund for their age, than cod elsewhere within the northern cod complex. The productivity and recruitment potential of coastal cod off Labrador may thus be much lower than that of offshore northern cod or of inshore cod farther south, implying that a more conservative management strategy may be required for cod from coastal Labrador than traditionally practised for northern cod inhabiting less harsh environments. Relatively high F ST and R ST measures of population structure suggest that important barriers to gene flow exist among five components that include two inshore (Gilbert and Trinity Bay) and three offshore cod aggregations on the north‐east Newfoundland Shelf and the Grand Bank. D A and D SW estimates of genetic distance that involve Gilbert Bay cod are approximately three‐ and 10–fold larger, respectively, than estimates not involving Gilbert Bay cod. The differences between inshore cod from Gilbert Bay and Trinity Bay raise the possibility that other genetically distinguishable coastal populations may exist, or may have existed prior to the northern cod fishery collapse. Harvesting strategies for northern cod should recognize the existence of genetic diversity between inshore and offshore components as well as among coastal components.

Identification of three genes expressed primarily during development in Physarum polycephalum - J. Bailey; L. J. Cook; R. Kilmer-Barber; E. Swanson; L. Solnica-Krezel; K. Lohman; W. F. Dove; J. Dee; R. W. Anderson (Archives of Microbiology, 1999)

Mammalian biogeography of the Alexander Archipelago of Alaska: a north temperate nested fauna - Chris J. Conroy; John R. Demboski; Joseph A. Cook (Journal of Biogeography, 1999)
Summary Aim A large number of studies have analysed the distribution of mammals within archipelagos, yet few have focused on islands that were heavily glaciated and subsequently colonized following deglaciation. Location We explored the relative effects of island area and isolation on faunal composition based on twenty‐three mammalian taxa of twenty‐four islands of the Alexander Archipelago, Southeast Alaska. Methods We used regression of log‐transformed variables and several indices of nestedness. Results These faunas showed significant nested structure using tests of nestedness and regression models. Unlike most landbridge and mainland archipelagos studied previously, isolation appears to be the primary factor determining patterns of species richness. Main conclusions Colonization ability of particular taxa, rather than extinction, has determined this nested structure. We suggest that other higher latitude archipelagos may show similar historical patterns.

Abstracts of papers presented at an international workshop on management of soilborne pathogens sponsored by the United States-Israel binational agricultural research and development fund (bard) - R. J. Cook; J. Katan; I. Chet; J. Katan; R. Rodriguez-Kabana; C. R. Taylor; J. W. Kloepper; M. M. Satour; G. L. Lazarovits; K. L. Conn; M. Tenuta; G. Kritzman; et al. (Phytoparasitica, 1998)

Comparison of Ceralure and Trimedlure Controlled-Release Formulations for Male Mediterranean Fruit Flies in C&C Traps - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1998)

Tree-ring records from New Zealand: long-term context for recent warming trend - R. D. D'Arrigo; E. R. Cook; M. J. Salinger; J. Palmer; P. J. Krusic; B. M. Buckley; R. Villalba (Climate Dynamics, 1998)

Sea-level pressure variability around Antarctica since A.D. 1750 inferred from subantarctic tree-ring records - R. Villalba; E. R. Cook; R. D. D'Arrigo; G. C. Jacoby; P. D. Jones; M. J. Salinger; J. Palmer (Climate Dynamics, 1997)

A CHANGING TEMPERATURE RESPONSE WITH ELEVATION FOR LAGAROSTROBOS FRANKLINII IN TASMANIA, AUSTRALIA - B. M. BUCKLEY; E. R. COOK; M. J. PETERSON; M. BARBETTI (Climatic Change, 1997)

Improved Controlled-Release Formulations for a New Trap Design for Male Mediterranean Fruit Flies: The C&C Trap - J. D. Warthen; R. T. Cunningham; B. A. Leonhardt; J. M. Cook; J. W. Avery; E. M. Harte (Journal of Chemical Ecology, 1997)

Migration between nests in the Australian arid‐zone ant Rhytidoponera sp. 12 revealed by DGGE analyses of mitochondrial DNA - W. Tek Tay; J. M. Cook; D. J. Rowe; R. H. Crozier (Molecular Ecology, 1997)
Denaturing gradient gel electrophoresis (DGGE) of a PCR‐amplified region of the mitochondrial DNA (mtDNA) including a large part of the cytochrome b gene revealed four haplotypes among worker ants from 75 colonies of the queenless ant Rhytidoponera sp. 12. The DGGE results were checked by sequencing examples of the haplotypes; all changes were transitions and two haplotypes differed by only a single substitution. Previous work (e.g. Crozier et al. 1984) showed that intranest relatedness is low for nuclear genes yet neighbouring nests are related; gene flow via winged males appeared the best explanation for this phenomenon. Two mtDNA haplotypes were found in 34.7% of the colonies studied, showing that female movement also occurs between nests. Migration of mated individuals on such a large scale when the number of reproductives is relatively small is unexpected (Crozier & Pamilo 1996). An observed tendency to clumping of the haplotypes is in accordance with the wingless nature of the female dispersers.

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)

Complementation with an avian influenza virus is required for synthesis of M protein of a human strain in chicken erythrocytes - R. F. Cook; R. J. Avery; N. J. Dimmock (Archives of Virology, 1980)

Taxonomic studies on strains of avian infectious bronchitis virus using neutralisation tests in tracheal organ cultures - J. H. Darbyshire; J. G. Rowell; Jane K. A. Cook; R. W. Peters (Archives of Virology, 1979)

Growth comparisons of avian infectious bronchitis virus strains in organ cultures of chicken tissues - J. H. Darbyshire; Jane K. A. Cook; R. W. Peters (Archives of Virology, 1978)

The use of chicken tracheal organ cultures for the isolation and assay of avian infectious bronchitis virus - Jane K. A. Cook; J. H. Darbyshire; R. W. Peters (Archives of Virology, 1976)

Aromatic metabolism in the fungi. Growth of Rhodotorula mucilaginosa in p-hydroxybenzoate-limited chemostats and the effect of growth rate on the synthesis of enzymes of the 3-oxoadipate pathway - Timothy J. Huber; John R. Street; Alan T. Bull; Keith A. Cook; Ronald B. Cain (Archives of Microbiology, 1975)

Sectional notes - W. B. Ward; Allan Purdy; Marx Koeiinke; H. J. Evans; Harrold Mattson; E. B. Tussing; Harold T. Cook; M. R. Harris; R. E. Goodwin; W. N. Keenan (American Journal of Potato Research, 1947)